Adhesive sheet

By using the combination of acrylic polymer and high content increased adhesive resin in the adhesive to use the combination of acrylic polymers and high content, the problem of reducing the adhesion under the contact of the oil division or water -based solvent is solved. And good oil resistance and water -resistant solvent.

CN119384475AActive Publication Date: 2025-01-28NITTO DENKO CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202280097488.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2022-12-12
Publication Date
2025-01-28
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The adhesive strength of the existing adhesive sheet is easily reduced when it comes into contact with an oil or an aqueous solvent, and it is difficult to take into account both high adhesion and oil resistance and water resistance solvent resistance.

Method used

The acrylic polymer containing acrylic orthopedia as a monomer is used, and the content of adhesive resin is added to the adhesive layer to ensure that the content of adhesive resin is greater than 10 times that of the acrylic polymer. The distension of the layer is below 100.

Benefits of technology

Effectively improve the adhesion and inhibit the decrease in adhesion force caused by the contact with oil or water -based solvents, and achieve high -level oil resistance and water resistance solvent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384475A_ABST
    Figure CN119384475A_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet having an adhesive layer containing an acrylic polymer and a tackifying resin. The acrylic polymer is a polymer containing a monomer component of n-heptyl acrylate. Relative to 100 parts by weight of the acrylic polymer, the content of the tackifying resin is more than 10 parts by weight. The adhesive layer has a degree of swelling with respect to ethyl acetate of 100 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-108034 filed on July 4, 2022, and the entire contents of this application are incorporated herein by reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives, hereinafter the same) are in a soft solid (viscoelastic) state within a temperature range near room temperature, and have the property of being adhered to an adherend by pressure. Utilizing this property, adhesives are widely used in various industrial fields, from home appliances to automobiles, various machinery, electronic equipment, etc., typically in the form of an adhesive sheet containing a layer of the adhesive, for the purpose of bonding components, surface protection, etc.

[0004] Among adhesive sheets, there are adhesive sheets for fixing components in portable devices such as mobile phones, smart phones, and tablet computers. Such portable devices are devices for carrying and use, so secretions such as sebum, hand dirt, chemicals such as cosmetics, hair dressing, moisturizers, sunscreens, or oils contained in foods are easy to adhere to. In particular, portable devices of the touch panel method that have been popularized in recent years have a display unit / input unit that also functions as an input unit. The user directly contacts the surface of the display unit / input unit with the fingertips to operate, so there are many opportunities for oils to adhere via the fingertips. In addition, among the so-called wearable devices, there are wearable devices that are worn and used in contact with the skin. In such a usage method, there are many opportunities to be exposed to oils such as chemicals applied to sebum and skin. Therefore, the adhesive sheet used for portable devices preferably has less reduction in adhesive force caused by contact with oil. As technical documents for suppressing the reduction in adhesive force caused by contact with oil, Patent Document 1 and Patent Document 2 can be cited.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-132911

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-165977 Summary of the invention

[0009] Problems to be solved by the invention

[0010] With the high performance and high functionality of portable devices, it is required to further improve the adhesive force in the adhesive sheet used for the fixation of components. In addition, due to the improvement of hygiene awareness in recent years, there is a tendency to increase the chance of using aqueous solvents such as water and lower alcohols in order to keep portable devices clean. Therefore, for the adhesive sheet used for portable devices, it is expected that even for contact with aqueous solvents, the reduction of adhesive force is less. However, in the field of adhesives, there is usually a compromise between the resistance to aqueous solvents and the resistance to oil. Therefore, it is not easy to achieve an adhesive sheet with high adhesive force and less reduction of adhesive force even if it contacts with oil or aqueous solvents.

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a PSA sheet capable of achieving both high levels of adhesive strength, suppression of reduction in adhesive strength due to contact with oil components, and suppression of reduction in adhesive strength due to contact with an aqueous solvent.

[0012] Means used to solve problems

[0013] According to this specification, an adhesive sheet having an adhesive layer comprising an acrylic polymer and a tackifier resin is provided. The acrylic polymer is a polymer of a monomer component comprising n-heptyl acrylate. The content of the tackifier resin in the above-mentioned adhesive layer is an amount greater than 10 parts by weight relative to 100 parts by weight of the above-mentioned acrylic polymer. The swelling degree of the above-mentioned adhesive layer to ethyl acetate is 100 or less. By using an acrylic polymer comprising n-heptyl acrylate as a monomer component, and making the content of the tackifier resin relative to 100 parts by weight of the above-mentioned acrylic polymer greater than 10 parts by weight under the condition that the swelling degree of the adhesive layer is 100 or less, the adhesive force can be effectively improved, and the reduction of the adhesive force caused by contact with oil can be suppressed. In addition, by using n-heptyl acrylate as a monomer component of the acrylic polymer, the reduction of the adhesive force caused by contact with an aqueous solvent can be appropriately suppressed. That is, according to the above-mentioned structure, it is possible to take into account the adhesive force, the suppression of the reduction of the adhesive force caused by contact with the oil (oil resistance) and the suppression of the reduction of the adhesive force caused by contact with an aqueous solvent (water-resistant solvent property) at a high level.

[0014] In some preferred embodiments, the monomer component contains 5.0 wt % or more of a carboxyl group-containing monomer. With this composition of monomer components, a PSA sheet with higher adhesive strength tends to be obtained.

[0015] In some preferred embodiments, the adhesive composition for forming the adhesive layer comprises an isocyanate crosslinking agent and an epoxy crosslinking agent. By using the isocyanate crosslinking agent and the epoxy crosslinking agent in combination, the swelling degree of the adhesive layer can be properly adjusted, and an adhesive sheet that takes into account high levels of adhesion, oil resistance, and water solvent resistance can be properly achieved.

[0016] In some preferred embodiments, the adhesive layer includes a phenolic tackifying resin as the tackifying resin. The adhesive force can be effectively improved by using an acrylic polymer including n-heptyl acrylate as a monomer component and a phenolic tackifying resin in combination.

[0017] Some preferred embodiments of the adhesive layer include a terpene phenol resin as the phenolic tackifying resin. By making the adhesive layer contain a terpene phenol resin, the adhesive force can be effectively improved. The content of the terpene phenol resin is preferably 20 parts by weight or more relative to 100 parts by weight of the acrylic polymer.

[0018] In some embodiments, the adhesive composition for forming the adhesive layer containing the above-mentioned phenolic tackifying resin preferably contains an isocyanate crosslinking agent and an epoxy crosslinking agent in combination. By using an acrylic polymer containing n-heptyl acrylate as a monomer component, a phenolic tackifying resin, an isocyanate crosslinking agent, and an epoxy crosslinking agent in combination, an adhesive sheet that takes into account high levels of adhesion, oil resistance, and water solvent resistance can be more appropriately achieved.

[0019] In some embodiments, the weight average molecular weight (Mw) of the acrylic polymer is preferably greater than 500,000. According to this embodiment, a PSA sheet having high levels of adhesive strength, oil resistance, and water solvent resistance can be easily obtained.

[0020] Some preferred embodiments of the PSA sheet have a 180 degree peel strength to a stainless steel plate (adhesion to SUS) of 8.0 N / 10 mm or more. The PSA sheet having such adhesion to SUS can exhibit high member fixing performance.

[0021] Some preferred adhesive sheets are double-sided adhesive sheets. Double-sided adhesive sheets are used by attaching one surface and the other surface of the adhesive sheet to adherends, so oil and aqueous solvents easily penetrate into the adhesive interface with these adherends. Therefore, it is particularly meaningful to apply the technology disclosed herein to suppress the reduction of adhesive force caused by the above oil.

[0022] Some preferred adhesive sheets are double-sided adhesive sheets having a resin film as a supporting substrate and the adhesive layer disposed on one surface and the other surface of the supporting substrate. The double-sided adhesive sheet of this configuration is advantageous from the viewpoint of processability and shape retention (e.g., suppression of protrusion) to a desired shape.

[0023] The adhesive sheet disclosed herein can take into account the adhesive force, the suppression of the reduction of the adhesive force caused by contact with the oil component, and the suppression of the reduction of the adhesive force caused by contact with the aqueous solvent at a high level, and is therefore suitable for fixing components in, for example, portable devices (e.g., portable electronic devices such as smart phones). Therefore, according to this specification, a portable device using any adhesive sheet disclosed herein is provided, in other words, a portable device including the adhesive sheet is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.

[0025] Figure 2 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0026] Figure 3 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0027] Figure 4 This is a front view schematically showing an example of a portable device (portable electronic device) including a pressure-sensitive adhesive sheet. DETAILED DESCRIPTION

[0028] Hereinafter, a preferred embodiment of the present invention will be described. It should be noted that, for matters that are not specifically mentioned in this specification but are necessary for the implementation of the present invention, those skilled in the art can understand them based on the teachings for the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in the art. In addition, in the following drawings, the same reference numerals are sometimes used to illustrate components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, in order to clearly illustrate the present invention, the embodiments described in the drawings are schematically illustrated and do not necessarily accurately represent the size and scale of the adhesive sheet of the present invention actually provided as a product.

[0029] In this specification, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in the temperature range near room temperature as described above, and has the property of being easily adhered to an adherend by pressure. The so-called adhesive herein is defined as "CADahlquist, "Adhesion: Fundamental and Practice", McLaren & Sons, (1966) P.143", which generally has a complex tensile elastic modulus E * (1Hz)<10 7 dyne / cm 2A material having the above properties at 25°C.

[0030] In this specification, carbon from biomass refers to carbon (renewable carbon) from biomass materials, i.e., materials from renewable organic resources. The above-mentioned biomass materials typically refer to materials from biological resources (typically plants that perform photosynthesis) that can be continuously reproduced as long as there is sunlight, water and carbon dioxide. Therefore, materials from fossil resources that have been exhausted due to use after mining (fossil resource materials) do not belong to the concept of biomass materials mentioned here. The biomass carbon ratio of the adhesive layer and the adhesive sheet, that is, the proportion of carbon from biomass in the total carbon contained in the adhesive layer and the adhesive sheet can be estimated based on the carbon isotope content of mass number 14 measured according to ASTM D6866.

[0031] <Composition of Adhesive Sheet>

[0032] The adhesive sheet disclosed herein is constituted by containing an adhesive layer. The above-mentioned adhesive sheet, for example, can be the form of a substrate-free double-sided adhesive sheet having a first adhesive face constituted by one surface of the adhesive layer and a second adhesive face constituted by another surface of the adhesive layer. Alternatively, the adhesive sheet disclosed herein can be the form of an adhesive sheet with a substrate obtained by laminating the above-mentioned adhesive layer on one side or both sides of a supporting substrate. Hereinafter, the supporting substrate is sometimes referred to as "substrate". It should be noted that the concept of the adhesive sheet mentioned herein may include articles referred to as adhesive tapes, adhesive labels, adhesive films, etc. The adhesive sheet disclosed herein can be in a roll shape or in a monolithic shape. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0033] The structure of a PSA sheet according to one embodiment is schematically shown in Figure 1 The adhesive sheet 1 is formed in the form of a double-sided adhesive sheet without a substrate and composed of an adhesive layer 21. The adhesive sheet 1 is used by sticking a first adhesive surface 21A composed of one surface (first surface) of the adhesive layer 21 and a second adhesive surface 21B composed of the other surface (second surface) of the adhesive layer 21 to different parts of the adherend. The parts where the adhesive surfaces 21A and 21B are stuck can be respective parts of different components or different parts within a single component. Figure 1As shown, the adhesive sheet 1 before use (i.e., before being pasted on the adherend) can be a constituent element of an adhesive sheet 100 with a release liner in which the first adhesive surface 21A and the second adhesive surface 21B are protected by release liners 31 and 32, which are at least one side opposite to the adhesive layer 21 and are respectively the release surface. As the release liners 31 and 32, for example, it is preferred to use a release liner formed in the form of a single surface being a release surface by providing a release layer formed by a release treatment agent on a single surface of a sheet-like substrate (liner substrate). Alternatively, the release liner 32 can be omitted, and a release liner 31 with two surfaces being the release surface is used, which is overlapped with the adhesive sheet 1 and wound into a spiral shape, thereby forming an adhesive sheet with a release liner in a form (rolled form) in which the second adhesive surface 21B is in contact with the back surface of the release liner 31 and is protected.

[0034] The structure of a pressure-sensitive adhesive sheet according to another embodiment is schematically shown in Figure 2 The adhesive sheet 2 is formed in the form of a single-sided adhesive sheet with a substrate, and the single-sided adhesive sheet with a substrate has: a sheet-shaped supporting substrate (e.g., a resin film) 10 having a first surface 10A and a second surface 10B, and an adhesive layer 21 provided on the first surface 10A side. The adhesive layer 21 is fixedly provided on the first surface 10A side of the supporting substrate 10, that is, it is not intended to be separated from the supporting substrate 10. Figure 2 As shown, the adhesive sheet 2 before use may be a component of an adhesive sheet 200 with a release liner in which the surface (adhesive surface) 21A of the adhesive layer 21 is protected by a release liner 31 whose at least one side opposite to the adhesive layer 21 is a release surface. Alternatively, the release liner 31 may be omitted, and a supporting substrate 10 having a second surface 10B as a release surface may be used, and the adhesive sheet 2 may be rolled up so that the adhesive surface 21A is in contact with the second surface (back surface) 10B of the supporting substrate 10 and protected (rolled form).

[0035] The structure of a pressure-sensitive adhesive sheet according to another embodiment is schematically shown in Figure 3 The adhesive sheet 3 is formed in the form of a double-sided adhesive sheet with a substrate, and the double-sided adhesive sheet with a substrate has: a sheet-shaped supporting substrate (e.g., a resin film) 10 having a first surface 10A and a second surface 10B, a first adhesive layer 21 fixedly arranged on the first surface 10A side, and a second adhesive layer 22 fixedly arranged on the second surface 10B side. Figure 3As shown, the adhesive sheet 3 before use may be a constituent element of an adhesive sheet 300 with a release liner in which the surface (first adhesive surface) 21A of the first adhesive layer 21 and the surface (second adhesive surface) 22A of the second adhesive layer 22 are protected by release liners 31 and 32. Alternatively, the release liner 32 may be omitted, and a release liner 31 having two release surfaces may be used, which is overlapped with the adhesive sheet 3 and wound into a spiral shape, thereby constituting an adhesive sheet with a release liner in which the second adhesive surface 22A is in contact with the back surface of the release liner 31 and is protected (rolled shape).

[0036] It should be noted that in the double-sided adhesive sheet with a substrate, at least one of the first adhesive layer and the second adhesive layer (e.g., the first adhesive layer) may be the adhesive layer described below, and the other adhesive layer (e.g., the second adhesive layer) may be the adhesive layer disclosed herein, or may be an adhesive layer having a different composition from the adhesive layer disclosed herein (specifically, the above-mentioned one adhesive layer. For example, the first adhesive layer). Such another adhesive layer may be formed, for example, from a known or commonly used adhesive.

[0037] <Adhesive Layer>

[0038] The adhesive layer constituting the adhesive sheet disclosed herein comprises an acrylic polymer and a tackifying resin. The above-mentioned adhesive layer is typically an adhesive layer using the above-mentioned acrylic polymer as a base polymer. Such an adhesive layer is also referred to as an acrylic adhesive layer. It should be noted that the base polymer of the adhesive layer refers to the main component of the rubbery polymer (a polymer showing rubber elasticity in the temperature range near room temperature) contained in the adhesive layer. In addition, in this manual, in the absence of special description, "main component" refers to a component that content is greater than 50 weight %. In addition, about the following description of the component that can be contained in adhesive and adhesive layer, as long as there is no special description, it is possible to be applicable to the adhesive composition for forming an adhesive (layer).

[0039] In addition, in this specification, "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule is also referred to as an "acrylic monomer". Therefore, the acrylic polymer of this specification is defined as a polymer containing monomer units derived from acrylic monomers. It should be noted that, in this specification, "(meth)acryloyl" collectively refers to acryloyl and methacryloyl. Similarly, "(meth)acrylate" collectively refers to acrylate and methacrylate, and "(meth)acrylic acid" collectively refers to acrylic acid and methacrylic acid.

[0040] (Acrylic polymer)

[0041] As an acrylic polymer used in the technology disclosed herein, a polymer containing a monomer component of n-heptyl acrylate (n-HpA) is used. The inventors have found that, compared with an acrylic polymer obtained by polymerizing a monomer component of a composition obtained by replacing the above-mentioned n-HpA with other alkyl acrylates such as n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), an acrylic polymer obtained by polymerizing a monomer component containing n-HpA (i.e., an alkyl acrylate having a n-heptyl group at the ester end) is more suitable for realizing an adhesive sheet that takes into account adhesion, oil resistance and water solvent resistance at a high level. More specifically, for example, compared with a structure in which n-HpA is replaced with 2EHA, it is easy to increase adhesion while suppressing swelling, and, for example, compared with a structure in which n-HpA is replaced with BA, resistance to aqueous solvents is good. Its reason is not explained in a particularly restrictive manner, it is believed that the glass transition temperature of the polymer comprising n-HpA as a monomer unit is low, thus making the adhesive layer adhere well to the adherend so as to easily suppress oil content, aqueous solvent infiltration into the interface of the two, in addition, due to having a relatively long straight-chain side chain from n-HpA, therefore good compatibility with tackifying resin, therefore even if the content of tackifying resin is increased, it is also easy to suppress the reduction of the adhesive force caused by contact with oil content, and the side chain from the above-mentioned n-HpA is low in lipophilicity compared with the side chain from the alkyl acrylate with more carbon atoms, therefore it is easy to suppress swelling degree. In addition, the side chain from n-HpA is lower in hydrophilicity compared with the side chain from the alkyl acrylate with less carbon atoms (such as BA), therefore it is believed that it is easy to suppress the reduction of the adhesive force caused by contact with aqueous solvent (such as a mixed solvent of water and lower alcohols).

[0042] In some ways, the proportion of n-HpA in the monomer component of acrylic polymer is more than 50 weight % (for example, greater than 50 weight %) is appropriate, preferably more than 70 weight %, more preferably more than 80 weight %, further preferably more than 85 weight %, particularly preferably more than 90 weight %, can be more than 91 weight %, can be more than 92 weight %, can be more than 94 weight %, can be more than 94.5 weight %. By increasing the usage of n-HpA, there is a tendency to more effectively show its use effect. In some ways, the ratio of n-HpA in the monomer component can be more than 98 weight % or more than 99 weight %, or can be 100 weight %. On the other hand, from the perspective of easily suppressing the swelling degree of the adhesive layer and easily adjusting the balance of properties, in some embodiments, it is appropriate that the proportion of n-HpA in the monomer component is 99.5 wt % or less, preferably 97 wt % or less (for example, less than 97 wt %), more preferably 96 wt % or less, further preferably 95 wt % or less, and can be 94 wt % or less, 93 wt % or less, or 91 wt % or less.

[0043] The acrylic polymer may be copolymerized with an alkyl (meth)acrylate other than n-HpA (hereinafter also referred to as "optional alkyl (meth)acrylate"). As the optional alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used.

[0044] CH2=C(R 1 )COOR 2 (1)

[0045] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group. 2 It is a chain alkyl group having 1 to 20 carbon atoms (except for n-heptyl).

[0046] Examples of the optional alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl methacrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like. These optional (meth) alkyl acrylates can be used alone or in combination of two or more. As the (meth) alkyl acrylates that can be preferably used, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) can be listed. These optional (meth) alkyl acrylates can be used alone or in combination of two or more.

[0047] In some embodiments, from the viewpoint of facilitating the use effect of n-HpA, the proportion of the optional (meth) alkyl acrylate contained in the monomer component (the total proportion of them when two or more are used) is appropriately less than 50% by weight (for example, 49.5% by weight or less), preferably less than 47% by weight, more preferably 45% by weight or less, further preferably 40% by weight or less, 30% by weight or less, 10% by weight or less, 5% by weight or less, or 1% by weight or less. Regarding R in the above formula (1), 2 The optional (meth)acrylic acid alkyl ester is an alkyl acrylate having 8 or more carbon atoms or an alkyl methacrylate having 7 or more carbon atoms. From the viewpoint of oil resistance, the proportion of the optional (meth)acrylic acid alkyl ester contained in the monomer component (when two or more are used, the total proportion of the optional (meth)acrylic acid alkyl ester) is suitably 30 wt % or less, preferably 20 wt % or less, more preferably 10 wt % or less, and may be 5 wt % or less, 1 wt % or less, or 0.5 wt % or less. In addition, regarding R in the above formula (1), 2The optional (meth) alkyl acrylate is an alkyl (meth) acrylate having a carbon number of 6 or less. From the viewpoint of resistance to aqueous solvents, the proportion of the optional (meth) alkyl acrylate contained in the monomer component (the total proportion when two or more are used) is appropriately 30% by weight or less of the monomer component, preferably 20% by weight or less, more preferably 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.5% by weight or less. In some embodiments, the technology disclosed herein can be preferably implemented in a manner in which the monomer component does not substantially contain the optional (meth) alkyl acrylate.

[0048] It should be noted that, in the present specification, the monomer component substantially not containing monomer A (such as the optional (meth)acrylate alkyl ester mentioned above) means that the monomer A is at least not used intentionally, and unintentional inclusion of the monomer A, for example, about 0.01 wt % or less, is allowed.

[0049] In some embodiments, the monomer component may include an alkyl (meth)acrylate having an alkyl group derived from biomass at the ester end (hereinafter also referred to as "biomass (meth)acrylate alkyl ester".). In recent years, environmental issues such as global warming have gradually received attention, and it is expected to reduce the use of fossil resource materials such as petroleum. In such a case, it is also required to reduce the use of fossil resource materials in the field of adhesives. By using biomass (meth)acrylate alkyl ester, an acrylic adhesive that takes into account the suppression of dependence on fossil resource materials can be appropriately realized.

[0050] Biomass (meth) alkyl acrylate is not particularly limited, for example, an ester of an alkanol from biomass and (meth) acrylic acid from biomass or not from biomass. Examples of alkanols from biomass include biomass ethanol, alkanols from plant raw materials such as palm oil or palm kernel oil, coconut oil, castor oil, etc. In the case where the carbon number of the alkanol from biomass is more than 3, the alkanol can be a straight chain or a branched chain. In some embodiments, as a biomass (meth) alkyl acrylate used in the synthesis of acrylic polymers, an ester of an alkanol from biomass and (meth) acrylic acid not from biomass can be used. In the biomass (meth) alkyl acrylate, the more carbon atoms of the alkanol, the higher the proportion of the number of carbons from biomass in the total number of carbons contained in the biomass (meth) alkyl acrylate, that is, the biomass carbon ratio of the (meth) alkyl acrylate. Therefore, in the above-mentioned biomass (meth) alkyl acrylate, from the perspective of reducing the dependence on fossil resource materials, it is desirable that the carbon number of the alkyl from biomass is more. On the other hand, when the carbon number of the alkyl group constituting the alkyl (meth)acrylate is too large, there is a tendency that the alkyl ester swells excessively due to contact with oil, and the oil resistance tends to be reduced. In addition, it may become disadvantageous from the perspective of productivity such as synthesis, operability, and cost. In the method of using an ester of a biomass-derived alkanol and a non-biomass-derived (meth)acrylic acid as the biomass alkyl (meth)acrylate, it is desirable to use a material that strikes a balance between adhesive properties and reduced dependence on fossil resource materials (more specifically, the biomass carbon ratio of the above-mentioned alkyl (meth)acrylate).

[0051] In some preferred embodiments, as n-heptyl acrylate, n-heptyl acrylate from biomass (biomass n-HpA) can be used. By using biomass n-HpA, the effect of the technology disclosed herein can be achieved while reducing the dependence on fossil resource materials. The above-mentioned biomass n-HpA is an ester of an alkanol from biomass and an acrylic acid from biomass or not from biomass, for example, an ester of an alkanol from biomass and an acrylic acid from not from biomass can be used. In this compound, only the straight-chain heptyl group comes from biomass.

[0052] The proportion of biomass (meth) alkyl acrylate (preferably biomass n-HpA) in the monomer component of the above-mentioned acrylic polymer is, for example, 50% by weight or more (for example, greater than 50% by weight) in some embodiments, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, particularly preferably 90% by weight or more, 92% by weight or more, 94% by weight or more, or 96% by weight or more. In addition, the proportion of biomass (meth) alkyl acrylate (preferably biomass n-HpA) in the monomer component is less than 97% by weight, in some embodiments, it can be 95% by weight or less, 93% by weight or less, or 91% by weight or less. In other embodiments, the proportion of biomass (meth) alkyl acrylate in the monomer component can be 90% by weight or less, 70% by weight or less, 50% by weight or less, 30% by weight or less, 10% by weight or less, or 1% by weight or less.

[0053] In some embodiments, the monomer component of the acrylic polymer preferably includes a carboxyl group-containing monomer. In addition to being able to contribute to the improvement of adhesive strength by improving cohesiveness due to its polarity, the carboxyl group-containing monomer can also inhibit excessive swelling of the adhesive layer to oil components and inhibit the reduction of adhesive strength caused by contact with oil components (for example, the adhesive strength retention rate R described below). A In addition, the carboxyl group can become a crosslinking point of the acrylic polymer, so there is an advantage that the swelling degree of the adhesive layer can be easily adjusted.

[0054] Examples of carboxyl-containing monomers include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. Among them, preferred carboxyl-containing monomers include AA and MAA. AA is particularly preferred. The carboxyl-containing monomers may be used alone or in combination of two or more.

[0055] The ratio of the carboxyl-containing monomer in the monomer component of acrylic polymer can be, for example, more than 0.5 wt %, or more than 1.0 wt % or more than 2.0 wt %. In some ways, it is appropriate that the ratio of the carboxyl-containing monomer in the monomer component of acrylic polymer is greater than 3.0 wt %, preferably more than 3.5 wt %, preferably more than 4.0 wt %, more preferably more than 4.5 wt % or more than 5.0 wt %. By increasing the consumption of the carboxyl-containing monomer, there is a tendency to suppress the adhesive force caused by contact with oil more well, and there is also a tendency to suppress swelling degree. In some ways, the ratio of the carboxyl-containing monomer in the monomer component can be greater than 5.0 wt %, or more than 5.5 wt %, or more than 6.0 wt %, or more than 7.0 wt %, or more than 8.0 wt % (for example, greater than 8.0 wt %), or more than 9.0 wt %. In addition, the amount of carboxyl-containing monomers is, for example, appropriate for less than 20% by weight of all monomer components, and from the viewpoint of suppressing the adhesive force reduced by contact with an aqueous solvent, preferably less than 15% by weight, more preferably less than 12% by weight. In some ways, the amount of the above-mentioned carboxyl-containing monomers can be less than 10% by weight, less than 9% by weight, less than 8% by weight, less than 6% by weight, or less than 5% by weight. By appropriately adjusting the amount of carboxyl-containing monomers within the above range, it is possible to balance adhesive force, oil resistance and water-resistant solvent resistance.

[0056] The acrylic polymer may be copolymerized with a functional group-containing monomer other than the carboxyl group-containing monomer. Hereinafter, the functional group-containing monomer other than the carboxyl group-containing monomer is also referred to as "functional group-containing monomer B". Examples of the functional group-containing monomer B that can introduce a functional group that can serve as a crosslinking base into the acrylic polymer or contribute to improving the adhesive strength include hydroxyl (OH group)-containing monomers (hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate, etc.), acid anhydride group-containing monomers, amide group-containing monomers ((meth)acrylamide, N,N-dimethyl (meth)acrylamide, etc.), amino group-containing monomers (aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, etc.), epoxy group-containing monomers, cyano group-containing monomers, ketone group-containing monomers, monomers having a nitrogen atom-containing ring (N-vinyl-2-pyrrolidone, N-(meth)acryloylmorpholine, etc.), alkoxysilyl group-containing monomers, and imide group-containing monomers. The functional group-containing monomer B may be used alone or in combination of two or more. In the embodiment in which the monomer component constituting the acrylic polymer includes the functional group-containing monomer B, the monomer component may include a carboxyl group-containing monomer or may not include substantially any carboxyl group-containing monomer.

[0057] In the case where the monomer component constituting the acrylic polymer includes the above-mentioned functional group-containing monomer B, the content of the functional group-containing monomer B in the monomer component is not particularly limited. From the viewpoint of appropriately exerting the effect based on the use of the functional group-containing monomer B, the content of the functional group-containing monomer B in the monomer component can be, for example, more than 0.1 wt %, more than 0.5 wt % is appropriate, and can be more than 1 wt %. In addition, from the viewpoint of easily obtaining the balance of oil resistance and water-resistant solvent in the monomer component comprising n-HpA, the content of the functional group-containing monomer B in the monomer component is appropriate to be less than 40 wt %, preferably less than 20 wt %, and can be less than 10 wt % (for example, less than 5 wt %). In some ways, the content of the functional group-containing monomer B in the monomer component is, for example, less than 3 wt %, can be less than 1 wt %, can be less than 0.5 wt %, can be less than 0.3 wt %, and can also be less than 0.1 wt %. The technology disclosed herein can preferably be implemented in a manner that the monomer component of the acrylic polymer does not substantially contain the functional group-containing monomer B.

[0058] In addition, when a hydroxyl-containing monomer is used as the above-mentioned functional group-containing monomer B, its content can be, for example, about 0.001% by weight or more of the total monomer components, can be about 0.01% by weight or more, or can be about 0.02% by weight or more. In addition, it is appropriate that the content of the hydroxyl-containing monomer is about 10% by weight or less in the total monomer components, preferably about 5% by weight or less, and more preferably about 2% by weight or less. In some embodiments, the content of the hydroxyl-containing monomer in the monomer component can be, for example, less than 1% by weight, less than 0.5% by weight, less than 0.3% by weight, less than 0.1% by weight, or less than 0.01% by weight. The monomer component of the acrylic polymer may not substantially contain a hydroxyl-containing monomer. According to the technology disclosed herein, the desired effect can be achieved without relying on a hydroxyl-containing monomer.

[0059] In the mode that the monomer component constituting acrylic polymer includes carboxyl-containing monomer, from the viewpoint of effectively bringing into play the effect of copolymerizing carboxyl-containing monomer, the proportion that carboxyl-containing monomer shares in the functional group-containing monomer whole (comprising the functional group-containing monomer whole of carboxyl-containing monomer) contained in the monomer component is more than 30 weight % is appropriate, preferably more than 50 weight %, more preferably more than 70 weight %, further preferably more than 80 weight %, particularly preferably more than 90 weight %, for example, can be more than 95 weight %, can be more than 97 weight %, can be more than 98 weight %, can be more than 99 weight % (for example, more than 99.9 weight %). The upper limit of the proportion that carboxyl-containing monomer shares in the above-mentioned functional group-containing monomer whole is 100 weight %, which is equivalent to the mode that does not use functional group-containing monomer B. In some ways, the proportion that carboxyl-containing monomer shares in the above-mentioned functional group-containing monomer whole can be, for example, less than 95 weight %.

[0060] For the purpose of improving cohesion, the monomer components constituting the acrylic polymer may also contain other copolymer components in addition to the above-mentioned functional group-containing monomers. Examples of other copolymer components include: vinyl ester monomers such as vinyl acetate; aromatic vinyl compounds such as styrene; (meth)acrylic acid cycloalkyl esters such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid aryl esters (such as phenyl (meth)acrylate), (meth)acrylic acid aryloxyalkyl esters (such as phenoxyethyl (meth)acrylate), and (meth)acrylic acid arylalkyl esters (such as benzyl (meth)acrylate) containing aromatic rings; olefin monomers; chlorine-containing monomers; isocyanate-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; etc. The above-mentioned other copolymer components can be used alone or in combination of two or more.

[0061] The amount of the other copolymerization components can be appropriately selected according to the purpose and use, and there is no particular restriction. From the perspective of appropriately exerting the effect brought by using other copolymerization components, it is appropriate to be more than 0.05 wt % in the monomer component, and it can be more than 0.5 wt %. In addition, from the perspective of easily taking into account oil resistance and water-resistant solvent resistance in the monomer component comprising n-HpA in a balanced manner, it is appropriate that the content of other copolymerization components in the monomer component is less than 20 wt %, preferably less than 10 wt %, more preferably less than 8 wt %, further preferably less than 5 wt %, for example, less than 3 wt %, and also less than 1 wt %. The technology disclosed herein can be preferably implemented in a manner that the monomer component does not substantially include other copolymerization components.

[0062] The monomer components constituting the acrylic polymer may include a multifunctional monomer having at least two (meth)acryloyl groups, vinyl groups, and other polymerizable functional groups (typically free radical polymerizable functional groups) having unsaturated double bonds. By using a multifunctional monomer as a monomer component, the cohesive force of the adhesive layer can be increased and the swelling degree can be suppressed. There are no particular restrictions on the multifunctional monomer, and examples thereof include: 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, neopentyl glycol di(meth)acrylate, and the like. The multifunctional monomers may be used alone or in combination of two or more.

[0063] The lower limit of the amount used in the case of using a multifunctional monomer is not particularly limited as long as it is greater than 0 wt %. The amount of a multifunctional monomer can be appropriately set in a manner that realizes the purpose of use of the multifunctional monomer. Usually, by making the amount of a multifunctional monomer be about 0.001 wt % or more (for example, about 0.01 wt % or more) of a monomer component, the use effect of the multifunctional monomer can be appropriately brought into play. In addition, in some ways, from the viewpoint of easily obtaining good adhesive force, it is appropriate that the amount of a multifunctional monomer is about 3 wt % or less of the above-mentioned monomer component, preferably about 2 wt % or less, more preferably about 1 wt % or less (for example, about 0.5 wt % or less). The monomer component constituting the acrylic polymer can be substantially composed of monofunctional monomers. That is, the above-mentioned monomer component may not include a multifunctional monomer.

[0064] The biomass carbon ratio of the monomer components constituting the acrylic polymer (the biomass carbon ratio of the acrylic polymer) can be, for example, 1% or more, 10% or more is appropriate, preferably 30% or more, more preferably 50% or more (for example, greater than 50%), 70% or more, 80% or more, or 90% to 100%. By designing in this way, an acrylic adhesive can be obtained that takes into account the suppression of dependence on fossil resource materials.

[0065] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, about 20°C to about 170°C (typically about 40°C to about 140°C).

[0066] The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.

[0067] The initiator used for the polymerization can be appropriately selected from the polymerization initiators known in the past according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide (BPO) and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; etc. As other examples of polymerization initiators, redox initiators based on the combination of peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used can be the usual amount, for example, it can be selected from the range of about 0.005 parts by weight to about 1 part by weight (typically about 0.01 parts by weight to about 1 part by weight) relative to 100 parts by weight of the total monomer components.

[0068] The weight average molecular weight (Mw) of acrylic polymer is not particularly limited, for example, it can be about 300,000 or more and about 5,000,000 or less. The Mw of acrylic polymer is usually preferably greater than 500,000 (for example, more than 550,000), more preferably 600,000 or more or greater than 600,000 (for example, more than 650,000). According to the acrylic polymer with this Mw, it is easy to obtain an adhesive sheet that takes into account adhesion, oil resistance and water-resistant solvent resistance at a high level. In some ways, the Mw of acrylic polymer can be more than 700,000, can be more than 800,000, can be more than 900,000 or more than 900,000, can be more than 950,000, can be more than 1,000,000 or more than 1,050,000 or more than 1,050,000, can be more than 1,150,000, can be more than 1,200,000, can be more than 1,200,000. In addition, from the viewpoints of the ease of synthesis of acrylic polymer, the ease of preparation of adhesive composition, coating, etc., it is appropriate that the Mw of acrylic polymer is usually about 3,000,000 or less (for example, less than 2,500,000). From the viewpoint of improving the adhesion between the adhesive layer and the adherend and facilitating the penetration of oil and aqueous solvent into the interface between the two, in some embodiments, the Mw of the acrylic polymer is preferably 2 million or less, more preferably 1.8 million or less, and may be 1.6 million or less, 1.5 million or less, 1.4 million or less, 1.3 million or less, 1.2 million or less, 1.1 million or less, 1 million or less, 900,000 or less, 850,000 or less, or 750,000 or less.

[0069] The Mw of the acrylic polymer can be measured by gel permeation chromatography (GPC) and obtained as a standard polystyrene conversion value. Specifically, it can be measured under the following conditions using a trade name "HLC-8220GPC" (manufactured by Tosoh Corporation) as a GPC measuring device. The same is true in the examples described below.

[0070] [GPC measurement conditions]

[0071] Sample concentration: 0.2 wt% (tetrahydrofuran solution)

[0072] Sample injection volume: 10 μL

[0073] Eluent: Tetrahydrofuran (THF)

[0074] Flow rate: 0.6 mL / min

[0075] Column temperature (measurement temperature): 40°C

[0076] column:

[0077] Sample column: 1 TSKguardcolumn SuperHZ-H + 2 TSKgel SuperHZM-H (manufactured by Tosoh Corporation)

[0078] Reference column: 1 piece, trade name "TSKgel SuperH-RC" (manufactured by Tosoh Corporation)

[0079] Detector: Differential Refractometer (RI)

[0080] Standard sample: polystyrene

[0081] (Tackifying resin)

[0082] Relative to 100 parts by weight of the above-mentioned acrylic polymer as a polymer of a monomer component comprising n-HpA, the adhesive layer disclosed herein comprises a tackifying resin greater than 10 parts by weight. By containing the tackifying resin of the amount, it is possible to effectively improve the bonding force. Relative to 100 parts by weight of acrylic polymer, the content of the tackifying resin can be, for example, more than 12 parts by weight, or more than 15 parts by weight or more than 18 parts by weight. In some ways, from the viewpoint of obtaining a higher effect of use, it is appropriate that the content of the tackifying resin is more than 18.5 parts by weight, preferably more than 20 parts by weight, more than 25 parts by weight, or more than 30 parts by weight, relative to 100 parts by weight of acrylic polymer. The acrylic polymer comprising n-HpA as a monomer unit has good compatibility with the tackifying resin, so it is possible to improve the bonding force by including more tackifying resin while maintaining a cohesive force suitable for suppressing the reduction of oil resistance and water resistance. In addition, the content of the tackifier resin relative to 100 parts by weight of the acrylic polymer can be, for example, 100 parts by weight or less or 90 parts by weight or less. From the viewpoint of better suppressing the reduction in adhesive strength caused by contact with oil, 80 parts by weight or less is appropriate, preferably 60 parts by weight or less (for example, 55 parts by weight or less), more preferably 50 parts by weight or less, and can be 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less.

[0083] There are no particular restrictions on the tackifying resin, and various tackifying resins such as phenolic tackifying resins, rosin tackifying resins, terpene tackifying resins, hydrocarbon tackifying resins, epoxy tackifying resins, polyamide tackifying resins, elastomer tackifying resins, and ketone tackifying resins can be used. Such tackifying resins can be used alone or in combination of two or more.

[0084] Examples of the phenolic tackifier resin include terpene phenol resins, hydrogenated terpene phenol resins, alkylphenol resins, and rosin phenol resins.

[0085] Terpene-phenol resin refers to a polymer containing terpene residues and phenol residues, and is a concept that includes copolymers of terpenes and phenolic compounds (terpene-phenol copolymer resins) and resins obtained by phenol-modifying homopolymers or copolymers of terpenes (phenol-modified terpene resins). Specific examples of terpenes constituting such terpene-phenol resins include monoterpenes such as α-pinene, β-pinene, and limonene (including d-form, l-form, and d / l-form (pine oil).) Hydrogenated terpene-phenol resin refers to a hydrogenated terpene-phenol resin having a structure obtained by hydrogenating such a terpene-phenol resin. It is sometimes also called hydrogenated terpene-phenol resin.

[0086] The alkylphenol resin is a resin obtained from an alkylphenol and formaldehyde (oil-based phenol resin). Examples of the alkylphenol resin include novolac-type alkylphenol resins and resol-type alkylphenol resins.

[0087] Rosin phenol resin is typically a phenol-modified product of rosin or various rosin derivatives (including rosin esters, unsaturated fatty acid-modified rosins, and unsaturated fatty acid-modified rosin esters). Examples of rosin phenol resin include rosin phenol resins obtained by adding phenol to rosin or the above-mentioned various rosin derivatives using an acid catalyst and performing thermal polymerization.

[0088] Among these phenolic tackifying resins, terpene phenol resins, hydrogenated terpene phenol resins and alkylphenol resins are preferred, terpene phenol resins and hydrogenated terpene phenol resins are more preferred, and terpene phenol resins are preferred among them.

[0089] Examples of rosin-based tackifying resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc. The same applies hereinafter); various other rosin derivatives; and the like. Examples of the above-mentioned rosin derivatives include: rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esterified rosin), and those obtained by esterifying modified rosin with alcohols (i.e., esterified rosin); unsaturated fatty acid-modified rosins obtained by modifying unmodified rosin or modified rosin with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid-modified rosin, or unsaturated fatty acid-modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; etc. Among them, rosin esters are preferred. Specific examples of rosin esters include esters of unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), such as methyl ester, triethylene glycol ester, glycerol ester, pentaerythritol ester, etc., but are not particularly limited.

[0090] Examples of terpene tackifying resins include polymers of terpenes (e.g., monoterpenes) such as α-pinene, β-pinene, d-limonene, l-limonene, and pinolene. It may be a homopolymer of one terpene or a copolymer of two or more terpenes. As a terpene homopolymer, α-pinene polymers, β-pinene polymers, and pinolene polymers may be cited.

[0091] Examples of hydrocarbon tackifying resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, their hydrogenated products (for example, alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins), their various modified products (for example, maleic anhydride modified products), coumarone resins, coumarone indene resins and other hydrocarbon resins.

[0092] In some ways, as tackifying resin, preferably use phenolic tackifying resin.By using phenolic tackifying resin, it is possible to satisfactorily improve adhesive force while suppressing the rise of swelling degree.Wherein, preferably terpene phenol resin.As tackifying resin, only one or more phenolic tackifying resins can be used, and phenolic tackifying resins and other tackifying resins (for example, rosin tackifying resins) can also be used in combination.The proportion shared by phenolic tackifying resin (for example, terpene phenol resin) in the tackifying resin whole contained in adhesive layer can be, for example, about 35 weight % or more, from the viewpoint of suitably bringing into play the effect of use of phenolic tackifying resin, preferably greater than about 50 weight %, can be about 70 weight % or more, can also be about 80 weight % or more.Technology disclosed herein can preferably be implemented in the mode of phenolic tackifying resin substantially all (for example, about 97 weight % or more or about 99 weight % or more, can also be 100 weight %).

[0093] In the method of using terpene phenol resin as a tackifying resin, the content of the terpene phenol resin can be, for example, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 9 parts by weight or more, 12 parts by weight or more, 15 parts by weight or more, or 18 parts by weight or more relative to 100 parts by weight of acrylic polymer. In some methods, from the viewpoint of obtaining a higher use effect, it is appropriate that the content of the terpene phenol resin is 18.5 parts by weight or more relative to 100 parts by weight of acrylic polymer, preferably 20 parts by weight or more, and can be 25 parts by weight or more. In addition, in some methods, from the viewpoint of oil resistance, etc., it is appropriate that the content of the terpene phenol resin is 80 parts by weight or less relative to 100 parts by weight of acrylic polymer, preferably 60 parts by weight or less (for example, 55 parts by weight or less), more preferably 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less. Here, the expression that the content of the terpene-phenol resin is X parts by weight or less relative to 100 parts by weight of the acrylic polymer is used to include both the meaning that the adhesive layer does not contain the terpene-phenol resin and that the terpene-phenol resin is contained in a ratio of X parts by weight or less relative to 100 parts by weight of the acrylic polymer. In some embodiments, the content of the terpene-phenol resin in the adhesive layer may be 10 parts by weight or less, or 5 parts by weight or less, 3 parts by weight or less, or 1 part by weight or less (e.g., 0 to 0.1 parts by weight) relative to 100 parts by weight of the acrylic polymer.

[0094] When using phenolic tackifying resin as tackifying resin, the containing ratio of tackifying resin (non-phenolic tackifying resin, such as rosin-based tackifying resin) other than phenolic tackifying resin in adhesive layer is suitable for example for less than 40 weight parts relative to 100 weight parts of acrylic polymer.Thus it is easy to suitably bring into play the effect comprising phenolic tackifying resin.In some ways, relative to 100 weight parts of acrylic polymer, the usage amount of non-phenolic tackifying resin is preferably less than about 20 weight parts (such as less than 20 weight parts), more preferably less than about 15 weight parts, can be less than about 10 weight parts, can also be less than about 5 weight parts.

[0095] In some embodiments, from the viewpoint of adhesion to an adherend, a tackifier resin T having a softening point of less than 150° C. is used as the tackifier resin. L . Tackifying resin T L The lower limit of the softening point is not particularly limited. In some embodiments, from the perspective of exerting appropriate cohesive force, the tackifying resin T L The softening point of the tackifier resin T is preferably about 60°C or higher, for example, about 80°C or higher, about 90°C or higher, or about 100°C or higher. L One type of tackifier resin having a softening point of less than 150° C. selected from the above-exemplified tackifier resins may be used alone or two or more types thereof may be used in combination.

[0096] In some embodiments, the tackifying resin T L Preferably, a phenolic tackifying resin is included. L The phenolic tackifying resin may be contained alone or in combination of two or more phenolic tackifying resins. L The phenolic tackifying resin and the non-phenolic tackifying resin may be contained in combination. As the non-phenolic tackifying resin, one or more of the tackifying resins listed above, which are appropriately selected from the tackifying resins other than the phenolic tackifying resin and have a softening point of less than 150° C., may be used alone or in combination. In some embodiments, the phenolic tackifying resin is contained in the tackifying resin T L The proportion of the total weight may be, for example, greater than about 50% by weight, about 65% by weight or more, or about 75% by weight or more. The technology disclosed herein may preferably be based on the tackifying resin T L The method is implemented in which substantially all (e.g., about 97% by weight or more, or about 99% by weight or more, or 100% by weight) of the phenolic tackifying resin is used.

[0097] Tackifying resin T L Content (including two or more tackifying resins T LThe total amount of the above mentioned components is not particularly limited. It is suitable to be 80 parts by weight or less relative to 100 parts by weight of the acrylic polymer. From the viewpoint of adhesion to the adherend, it is preferably 60 parts by weight or less (e.g., 55 parts by weight or less), more preferably 50 parts by weight or less, and may be 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less. In addition, the tackifying resin T may be 0.05% by weight or less relative to 100 parts by weight of the acrylic polymer. L The amount of the tackifier resin T may be, for example, 5 parts by weight or more, 7 parts by weight or more, 9 parts by weight or more, 12 parts by weight or more, 15 parts by weight or more, or 18 parts by weight or more. In some embodiments, from the perspective of improving the adhesive force, the tackifier resin T may be 100 parts by weight of the acrylic polymer. L The usage-amount is suitably 18.5 parts by weight or more, for example, preferably 20 parts by weight or more, and may be 25 parts by weight or more.

[0098] In some embodiments, the adhesive layer may contain a tackifying resin T L and a tackifying resin T having a softening point of 150°C or higher (e.g., 150°C to 200°C) H As a tackifying resin T H Among the tackifier resins exemplified above and having a softening point of 150° C. or higher, one type may be used alone or two or more types may be used in combination.

[0099] It should be noted that the softening point of the tackifying resin in this specification is defined as the value measured according to the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is quickly melted at the lowest possible temperature and filled into a ring placed on a flat metal plate, taking care not to generate bubbles. After cooling, the raised portion is cut off from the plane containing the upper end of the ring with a slightly heated knife. Next, a support (ring stand) is placed in a glass container (heating bath) having a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected until the depth reaches more than 90 mm. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and a ring filled with the sample are immersed in glycerin in a non-contact manner, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, a steel ball is placed in the center of the sample surface in the ring and is placed in a fixed position on the support. Next, keep the distance from the upper end of the ring to the glycerin surface at 50 mm, place a thermometer so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and heat the container. Use the flame of the Bunsen burner used for heating to be located between the center and the edge of the bottom of the container to make the heating uniform. It should be noted that the rate of increase in the bath temperature after reaching 40°C after the start of heating must be 5.0°C ± 0.5°C per minute. The sample gradually softens and flows down from the ring. The temperature when it finally contacts the bottom plate is read and used as the softening point. The softening point is measured twice or more at the same time, and the average value is used.

[0100] In some embodiments, the tackifying resin T L Preferably, the tackifier resin accounts for more than 50% by weight of the total amount of the tackifier resin contained in the adhesive layer. L By more effectively utilizing the tackifying resin T L Considering the effect of use, the tackifying resin T L The total amount of the tackifier resin contained in the adhesive layer is preferably 60% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 90% by weight or more, 95% by weight or more, or 98% by weight or more. In some preferred embodiments, the tackifier resin contained in the adhesive layer substantially only comprises tackifier resin T L In this method, the tackifying resin T L The ratio of the total amount of the tackifier resin contained in the adhesive layer is in the range of 99% by weight to 100% by weight.

[0101] In some ways, the above-mentioned tackifying resin may include a tackifying resin having a hydroxyl value of 40 mgKOH / g or more (e.g., greater than 40 mgKOH / g, preferably 45 mgKOH / g or more, and more preferably 50 mgKOH / g or more). Hereinafter, the tackifying resin having this hydroxyl value is sometimes referred to as a "high hydroxyl value resin". Acrylic polymers containing n-HpA as monomer units have good compatibility with such high hydroxyl value resins, so that the adhesion can be improved while taking into account oil resistance and water solvent resistance in a balanced manner by using the high hydroxyl value resin. In some ways, the hydroxyl value of the high hydroxyl value resin can be 60 mgKOH / g or more, 80 mgKOH / g or more, 90 mgKOH / g or more, or 100 mgKOH / g or more. The upper limit of the hydroxyl value of the high hydroxyl value resin is not particularly limited, for example, it can be about 200 mgKOH / g or less, about 160 mgKOH / g or less, or about 140 mgKOH / g or less. In some embodiments, from the viewpoint of adhesion to an adherend, the hydroxyl value of the high hydroxyl value resin is preferably about 125 mgKOH / g or less, about 115 mgKOH / g or less, or about 90 mgKOH / g or less.

[0102] As the high hydroxyl value resin, one or more tackifying resins appropriately selected from the tackifying resins having a hydroxyl value equivalent to the high hydroxyl value resin in the above-mentioned tackifying resins can be used alone or in combination. In some embodiments, the high hydroxyl value resin preferably includes a phenolic tackifying resin (e.g., a terpene phenol resin). The high hydroxyl value resin can contain one phenolic tackifying resin alone, or it can contain two or more phenolic tackifying resins in combination. In addition, the high hydroxyl value resin can be the above-mentioned tackifying resin T L , or it can be tackifying resin T H In some embodiments, it is preferred to use a tackifying resin T L High hydroxyl value resin. L The high hydroxyl value resin can suppress the decrease in oil resistance and water solvent resistance while increasing the amount of tackifier resin to improve the adhesive force.

[0103] Although not particularly limited, when a high hydroxyl value resin (for example, a high hydroxyl value resin having a hydroxyl value of greater than 40 mgKOH / g, preferably greater than 45 mgKOH / g, and more preferably greater than 50 mgKOH / g) is used, the amount of the high hydroxyl value resin used (when two or more high hydroxyl value resins are included, the total amount thereof) can be, for example, 5 parts by weight or more relative to 100 parts by weight of the acrylic polymer. From the viewpoint of obtaining a higher effect, it is preferably 10 parts by weight or more (for example, greater than 10 parts by weight), more preferably 12 parts by weight or more, 15 parts by weight or more, 18 parts by weight or more (for example, 18.5 parts by weight or more), 20 parts by weight or more, or 25 parts by weight or more. In addition, from the viewpoint of suppressing swelling and oil resistance, in some embodiments, the amount of the high hydroxyl value resin used is appropriately 80 parts by weight or less, preferably 60 parts by weight or less (e.g. 55 parts by weight or less), more preferably 50 parts by weight or less, and can be 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less, relative to 100 parts by weight of the acrylic polymer.

[0104] In some embodiments, the high hydroxyl value resin (for example, a high hydroxyl value resin having a hydroxyl value greater than 40 mgKOH / g, preferably greater than 45 mgKOH / g, and more preferably greater than 50 mgKOH / g) preferably accounts for more than 30% by weight of the total amount of the tackifying resin contained in the adhesive layer, and more preferably accounts for more than 50% by weight. Thus, the effect of improving the adhesive force while taking into account both oil resistance and water solvent resistance in a balanced manner can be satisfactorily achieved. In some embodiments, from the perspective of making it easier to exert the use effect of the high hydroxyl value resin, the proportion of the high hydroxyl value resin in the total amount of the tackifying resin contained in the adhesive layer is preferably 60% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 90% by weight or more, and can be 95% by weight or more, or 98% by weight or more. In some preferred embodiments, the tackifying resin contained in the adhesive layer substantially only contains high hydroxyl value resin. In this embodiment, the proportion of the high hydroxyl value resin in the total amount of the tackifying resin contained in the adhesive layer is in the range of 99% by weight to 100% by weight.

[0105] In some embodiments, the above-mentioned tackifying resin may include a tackifying resin having a hydroxyl value of less than 40 mgKOH / g (e.g., less than 30 mgKOH / g). Hereinafter, the tackifying resin having this hydroxyl value is sometimes referred to as a "low hydroxyl value resin". The hydroxyl value of the low hydroxyl value resin may be less than about 20 mgKOH / g, less than about 15 mgKOH / g, or less than about 10 mgKOH / g. There is no particular restriction on the lower limit of the hydroxyl value of the low hydroxyl value resin, and it may be substantially 0 mgKOH / g. The low hydroxyl value resin is preferably used in combination with a high hydroxyl value resin, which can contribute to the adjustment of adhesive properties, etc. Alternatively, the technology disclosed herein may also be implemented in a manner using only a low hydroxyl value resin as a tackifying resin.

[0106] As the low hydroxyl value resin, one or more tackifier resins selected from the above-mentioned tackifier resins having a hydroxyl value equivalent to that of the low hydroxyl value resin may be used alone or in combination. In some embodiments, the low hydroxyl value resin preferably includes a rosin-based tackifier resin. The hydroxyl value resin may include one rosin-based tackifier resin alone or in combination of two or more rosin-based tackifier resins. In addition, the low hydroxyl value resin may be the above-mentioned tackifier resin T L , or it can be tackifying resin T H In some embodiments, it is preferred to use a tackifying resin T L Low hydroxyl value resin.

[0107] Although there is no particular limitation, the amount of the low hydroxyl resin used in the case of using the low hydroxyl resin (the total amount of the low hydroxyl resins in the case of two or more) can be, for example, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, or 9 parts by weight or more relative to 100 parts by weight of the acrylic polymer. In addition, the amount of the low hydroxyl resin used relative to 100 parts by weight of the acrylic polymer is usually appropriate to be 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 4 parts by weight or less, or 2 parts by weight or less. Low hydroxyl resin may not be used.

[0108] Here, as the value of the hydroxyl value, there can be adopted a value measured by a potentiometric titration method specified in JIS K0070: 1992. The specific measurement method is as follows.

[0109] [Method for measuring hydroxyl value]

[0110] 1. Reagents

[0111] (1) As the acetylating agent, an acetylating agent obtained by taking about 12.5 g (about 11.8 mL) of acetic anhydride, adding pyridine thereto to make the total amount 50 mL, and stirring thoroughly was used. Alternatively, an acetylating agent obtained by taking about 25 g (about 23.5 mL) of acetic anhydride, adding pyridine thereto to make the total amount 100 mL, and stirring thoroughly was used.

[0112] (2) As a measurement reagent, a 0.5 mol / L potassium hydroxide ethanol solution was used.

[0113] (3) Separately, prepare toluene, pyridine, ethanol, and distilled water.

[0114] 2. Operation

[0115] (1) Accurately weigh about 2 g of a sample in a flat-bottom flask, add 5 mL of an acetylation reagent and 10 mL of pyridine, and install an air cooling tube.

[0116] (2) The flask was heated in a bath at 100°C for 70 minutes, then cooled naturally, 35 mL of toluene as a solvent was added from the top of the cooling tube and stirred, and then 1 mL of distilled water was added and stirred to decompose acetic anhydride. In order to complete the decomposition, the flask was heated in the bath again for 10 minutes and cooled naturally.

[0117] (3) The cooling tube was washed with 5 mL of ethanol and removed. Then, 50 mL of pyridine was added as a solvent and stirred.

[0118] (4) Use a volute pipette to add 25 mL of 0.5 mol / L potassium hydroxide ethanol solution.

[0119] (5) Potentiometric titration was performed using a 0.5 mol / L potassium hydroxide ethanol solution. The inflection point of the obtained titration curve was taken as the end point.

[0120] (6) In a blank test, the above (1) to (5) are carried out without adding a sample.

[0121] 3. Calculation

[0122] The hydroxyl value was calculated according to the following formula.

[0123] Hydroxyl value (mgKOH / g) = [(BC) × f × 28.05] / S + D

[0124] Here,

[0125] B: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the blank test (mL),

[0126] C: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the sample (mL),

[0127] f: Factor of 0.5 mol / L potassium hydroxide ethanol solution,

[0128] S: weight of the sample (g),

[0129] D: acid value,

[0130] 28.05: 1 / 2 of the molecular weight of potassium hydroxide, 56.11.

[0131] As the tackifying resin contained in the adhesive layer disclosed herein, from the viewpoint of increasing the biomass carbon ratio of the adhesive layer, a tackifying resin from a plant (plant-based tackifying resin) can be preferably used. As examples of plant-based tackifying resins, for example, the above-mentioned rosin-based tackifying resins and terpene-based tackifying resins can be cited. Plant-based tackifying resins can be used alone or in combination of two or more. The proportion of the plant-based tackifying resin in the total amount of the tackifying resin is preferably 30% by weight or more (for example, 50% by weight or more, typically 80% by weight or more). In some embodiments, the proportion of the plant-based tackifying resin in the total amount of the tackifying resin is 90% by weight or more (for example, 95% by weight or more, typically 99% to 100% by weight). The technology disclosed herein can preferably be implemented in a manner that does not substantially contain a tackifying resin other than the plant-based tackifying resin.

[0132] In the technology disclosed herein, the total content of the acrylic polymer and the tackifying resin in the adhesive layer is appropriately set to exert the effect brought by the technology disclosed herein, and is not limited to a specific range. From the viewpoint of better exerting the effect brought by the technology disclosed herein, it is appropriate that the total amount (total amount) of the acrylic polymer and the tackifying resin contained in the adhesive layer of some preferred embodiments is greater than 50% by weight, preferably about 70% by weight or more, more preferably about 90% by weight or more, and further preferably about 95% by weight or more (e.g., 95% by weight or more and 100% by weight or less or greater than or equal to 95% by weight and less than 100% by weight), and can be 97% by weight or more.

[0133] (Crosslinking agent)

[0134] In the technology disclosed herein, the adhesive composition used in forming the adhesive layer may contain a crosslinking agent as needed. The type of crosslinking agent is not particularly limited, and examples thereof include epoxy crosslinking agents, isocyanate crosslinking agents, Azoline crosslinking agent, aziridine crosslinking agent, melamine crosslinking agent, peroxide crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal chelate crosslinking agent, metal salt crosslinking agent, carbodiimide crosslinking agent, hydrazine crosslinking agent, amine crosslinking agent, silane coupling agent, etc. The crosslinking agent can be used alone or in combination of two or more. Among them, epoxy crosslinking agent, isocyanate crosslinking agent, The crosslinking agent of the present invention can be selected from the group consisting of oxazoline crosslinking agent, aziridine crosslinking agent, melamine crosslinking agent, and more preferably epoxy crosslinking agent, isocyanate crosslinking agent. By appropriately selecting and using the crosslinking agent, it is possible to satisfactorily achieve a cohesion degree of less than 100. It should be noted that the adhesive layer in the technology disclosed herein can contain the above-mentioned crosslinking agent in the form after the crosslinking reaction, the form before the crosslinking reaction, the form in which the crosslinking reaction is partially carried out, the form between them or a composite form, etc. The above-mentioned crosslinking agent is typically mainly contained in the adhesive layer in the form after the crosslinking reaction.

[0135] As the epoxy crosslinking agent, a compound having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. The epoxy crosslinking agent can be used alone or in combination of two or more.

[0136] Specific examples of epoxy crosslinking agents are not particularly limited, and examples thereof include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, etc. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "EPICRON CR-5L" manufactured by DIC Corporation, trade name "DENACOL EX-512" manufactured by Nagase Chemte X Co., Ltd., and trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.

[0137] The amount of epoxy crosslinking agent used is not particularly limited. For example, the amount of epoxy crosslinking agent used can be greater than 0 part by weight and less than or equal to about 1 part by weight (typically about 0.001 part by weight to about 1 part by weight) relative to 100 parts by weight of the acrylic polymer. From the viewpoint of suitably exerting the effect of improving cohesion, the amount of epoxy crosslinking agent used is about 0.005 parts by weight or more relative to 100 parts by weight of the acrylic polymer. It is preferably about 0.01 parts by weight or more (for example, greater than 0.01 parts by weight, or 0.015 parts by weight or more), and more preferably about 0.02 parts by weight or more (for example, greater than 0.02 parts by weight, or 0.025 parts by weight or more). In addition, from the viewpoint of improving adhesion to the adherend, the amount of the epoxy crosslinking agent used is appropriately about 0.5 parts by weight or less, preferably about 0.2 parts by weight or less, more preferably about 0.1 parts by weight or less (for example, less than 0.1 parts by weight), relative to 100 parts by weight of the acrylic polymer, and can be 0.07 parts by weight or less, can be 0.05 parts by weight or less, can be 0.04 parts by weight or less (for example, less than 0.04 parts by weight), can be less than 0.035 parts by weight, and can be 0.03 parts by weight or less.

[0138] As the isocyanate crosslinking agent, polyfunctional isocyanate (a compound having an average of two or more isocyanate groups per molecule, including a compound having an isocyanurate structure) can be preferably used. The isocyanate crosslinking agent can be used alone or in combination of two or more.

[0139] Examples of the polyfunctional isocyanate include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.

[0140] Specific examples of aliphatic polyisocyanates include: 1,2-ethylene diisocyanate; 1,2-butylene diisocyanate, 1,3-butylene diisocyanate, 1,4-butylene diisocyanate and other butylene diisocyanates; 1,2-hexylene diisocyanate, 1,3-hexylene diisocyanate, 1,4-hexylene diisocyanate, 1,5-hexylene diisocyanate, 1,6-hexylene diisocyanate, 2,5-hexylene diisocyanate and other hexylene diisocyanates; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, lysine diisocyanate and the like.

[0141] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0142] Specific examples of aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrobiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, Isocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene 1,4-diisocyanate, naphthylene 1,5-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, etc.

[0143] As preferred polyfunctional isocyanates, polyfunctional isocyanates having an average of three or more isocyanate groups per molecule can be exemplified. The trifunctional or higher isocyanates can be polymers (typically dimers or trimers) of difunctional or trifunctional or higher isocyanates, derivatives (e.g., addition reaction products of polyols and two or more molecules of polyfunctional isocyanates), polymers, etc. For example, polyfunctional isocyanates such as dimers of diphenylmethane diisocyanate or trimers of diphenylmethane diisocyanate, isocyanurates of hexamethylene diisocyanate (trimer adducts of isocyanurate structures), reaction products of trimethylolpropane and toluene diisocyanate, reaction products of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanates, polyether polyisocyanates, polyester polyisocyanates, etc. can be cited. Examples of commercially available products of the polyfunctional isocyanate include "DURANATE TPA-100" manufactured by Asahi Kasei Chemicals, "Coronate L" manufactured by Tosoh Corporation, "Coronate HL" manufactured by Tosoh Corporation, "Coronate HK" manufactured by Tosoh Corporation, "Coronate HX" manufactured by Tosoh Corporation, and "Coronate 2096" manufactured by Tosoh Corporation.

[0144] The amount of the isocyanate crosslinking agent used is not particularly limited, for example, it can be about 0.1 parts by weight or more relative to 100 parts by weight of the acrylic polymer. From the viewpoint of taking into account the adhesion, oil resistance and water solvent resistance, the amount of the isocyanate crosslinking agent used relative to 100 parts by weight of the acrylic polymer can be, for example, 0.5 parts by weight or more, 1.0 parts by weight or more is appropriate, 1.5 parts by weight or more is advantageous, preferably 2.0 parts by weight or more, more preferably greater than 2.5 parts by weight, 2.8 parts by weight or more, 3.0 parts by weight or more, and 3.5 parts by weight or more. In addition, relative to 100 parts by weight of the acrylic system, the amount of the above-mentioned isocyanate crosslinking agent used is appropriate to be less than 10 parts by weight, preferably less than 8.0 parts by weight, more preferably less than 7.0 parts by weight, and further preferably less than 6.0 parts by weight. It can be less than 5.0 parts by weight or less than 4.5 parts by weight.

[0145] In some preferred embodiments, as a crosslinking agent, an epoxy crosslinking agent and at least one crosslinking agent having a crosslinking functional group different from that of the epoxy crosslinking agent can be used in combination. According to the technology disclosed herein, by using a crosslinking agent other than an epoxy crosslinking agent (i.e., a crosslinking agent having a crosslinking reactive group different from that of the epoxy crosslinking agent, hereinafter also referred to as a "non-epoxy crosslinking agent") in combination with an epoxy crosslinking agent, it is possible to appropriately balance the adhesion and high holding power to different types of materials.

[0146] The type of non-epoxy crosslinking agent that can be used in combination with the epoxy crosslinking agent is not particularly limited, and can be appropriately selected from the above crosslinking agents. The non-epoxy crosslinking agent can be used alone or in combination of two or more.

[0147] In some preferred embodiments, an isocyanate crosslinking agent can be used as a non-epoxy crosslinking agent. For example, by using an epoxy crosslinking agent and an isocyanate crosslinking agent in combination, a more excellent adhesive property can be achieved. The relationship between the content of the epoxy crosslinking agent and the content of the non-epoxy crosslinking agent (preferably an isocyanate crosslinking agent) is not particularly limited. The content of the epoxy crosslinking agent can be, for example, less than about 1 / 10 of the content of the non-epoxy crosslinking agent (preferably an isocyanate crosslinking agent). From the perspective of more appropriately taking into account the adhesion and cohesion of the adherend, it is appropriate that the content of the epoxy crosslinking agent is less than about 1 / 30 of the content of the non-epoxy crosslinking agent, preferably less than about 1 / 50 (for example, less than about 1 / 60), more preferably less than about 1 / 75, and can be less than about 1 / 90. In addition, from the viewpoint of appropriately exerting the effect of using an epoxy crosslinking agent and a non-epoxy crosslinking agent (preferably an isocyanate crosslinking agent) in combination, the content of the epoxy crosslinking agent is usually about 1 / 1000 or more of the content of the non-epoxy crosslinking agent, for example, about 1 / 500 or more, preferably about 1 / 300 or more, more preferably 1 / 180 or more (for example, 1 / 150 or more), and further preferably 1 / 120 or more.

[0148] The total amount of the cross-linking agent used is not particularly limited. For example, it can be selected from a range of about 0.005 parts by weight or more (e.g., about 0.01 parts by weight or more, typically about 0.1 parts by weight or more) and about 10 parts by weight or less (e.g., about 8 parts by weight or less, preferably about 5 parts by weight or less) relative to 100 parts by weight of the acrylic polymer.

[0149] (Other additives)

[0150] In addition to the above-mentioned components, the adhesive composition may contain various additives commonly used in the field of adhesives, such as leveling agents, crosslinking aids, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, and light stabilizers, as needed. For such various additives, conventionally known substances can be used, which are not the characteristics of the present invention, so detailed description is omitted.

[0151] (Swelling degree)

[0152] The adhesive layer in the technology disclosed herein has a swelling degree of 100 or less for ethyl acetate. By using an acrylic polymer containing n-HpA as a monomer component, the content of the tackifying resin is greater than 10 parts by weight relative to 100 parts by weight of the acrylic polymer under the condition that the swelling degree is less than 100, the adhesive force can be effectively improved, and the adhesive force caused by contact with oil and aqueous solvents can be suppressed. Thus, it is possible to achieve an adhesive sheet that takes into account adhesive force, oil resistance and water-based solvent resistance at a high level. In some ways, from the viewpoint of improving oil resistance, the swelling degree of the adhesive layer is preferably less than 90, more preferably less than 80, can be less than 75, can be less than 70, can be less than 65, can be less than 60 (for example, less than 60). The lower limit of the swelling degree is not particularly limited, for example, it can be more than 10. From the viewpoint of adhesion to the adherend, in some ways, the swelling degree of the adhesive layer is more than 30 is appropriate, preferably more than 35, more preferably more than 40, can be more than 45 (for example, greater than 45), and can also be more than 50. The swelling degree of the adhesive layer is appropriately adjusted within the above range and is measured by the method described in the Examples below. The swelling degree can be adjusted by the adhesive composition such as the monomer composition, Mw of the acrylic polymer, tackifier resin, and crosslinking agent.

[0153] (Formation of Adhesive Layer)

[0154] The adhesive layer (layer containing adhesive) disclosed herein can be an adhesive layer formed by an aqueous adhesive composition, a solvent-based adhesive composition, a hot melt adhesive composition, or an active energy ray-curable adhesive composition. An aqueous adhesive composition refers to an adhesive composition in the form of an adhesive (adhesive layer forming component) contained in a solvent (aqueous solvent) having water as the main component, typically an aqueous adhesive composition containing what is called a water-dispersible adhesive composition (a composition in the form of at least a portion of the adhesive dispersed in water). In addition, a solvent-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in an organic solvent. As the organic solvent contained in the solvent-based adhesive composition, one or more of the organic solvents (toluene, ethyl acetate, etc.) that can be used in the above-mentioned solution polymerization can be used without particular limitation. The technology disclosed herein can be preferably implemented in a manner having an adhesive layer formed by a solvent-based adhesive composition from the viewpoint of adhesive properties, etc.

[0155] The adhesive layer disclosed herein can be formed by a method known in the past. For example, a method for forming an adhesive layer by applying an adhesive composition on a surface with peelability (peeling surface) or a non-peeling surface and drying it can be adopted. For the adhesive sheet with the structure of a substrate, for example, a method (direct method) can be adopted by directly applying (typically coating) an adhesive composition on the substrate and drying it to form an adhesive layer. In addition, it is also possible to adopt a method (transfer method) by applying an adhesive composition on a surface with peelability (peeling surface) and drying it to form an adhesive layer on the surface, and transferring the adhesive layer to the substrate. From the viewpoint of productivity, a transfer method is preferred. As the above-mentioned peeling surface, the surface of a peeling liner, the back side of the substrate that has been peeled off, etc. can be utilized. It should be noted that the adhesive layer disclosed herein is typically formed continuously, but is not limited to such a mode, for example, it can also be an adhesive layer formed into regular or irregular patterns such as dot-shaped and strip-shaped.

[0156] The adhesive composition can be applied using a conventionally known coater such as a gravure roll coater, a die coater, or a bar coater. Alternatively, the adhesive composition can be applied by dipping, curtain coating, or the like.

[0157] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature can be, for example, about 40°C to about 150°C, and is generally preferably about 60°C to about 130°C. After the adhesive composition is dried, it can be further aged for the purpose of regulating the migration of components in the adhesive layer, carrying out the crosslinking reaction, relaxing the strain that may exist in the adhesive layer, etc.

[0158] There is no particular restriction on the thickness of the adhesive layer, and it can be formed by, for example, an adhesive layer having an appropriate thickness in the range of 0.1 μm to 500 μm, depending on the application, the purpose of use, etc. In some embodiments, from the viewpoint of avoiding excessive thickening of the adhesive sheet, it is appropriate that the thickness of the adhesive layer is about 100 μm or less, preferably about 70 μm or less, more preferably about 50 μm or less, and further preferably about 35 μm or less. In some preferred adhesive sheets, the thickness of the adhesive layer can be about 30 μm or less (e.g., less than 30 μm), about 25 μm or less (e.g., less than 25 μm), about 22 μm or less, or about 20 μm or less (e.g., less than 20 μm). An adhesive layer with limited thickness can cope well with the requirements of thickness reduction and lightweighting. In addition, when the thickness of the adhesive layer is usually reduced, there is a tendency for the adhesive force to decrease. In addition, there is a tendency for the adhesion to the adherend to decrease, and oil and aqueous solvents to easily penetrate into the interface. According to the technology disclosed herein, by having a composition of an adhesive layer with a limited thickness, it is possible to achieve an adhesive sheet that takes into account the adhesion, oil resistance and water solvent resistance at a high level. From the perspective of adhesion to the adherend, in some ways, the lower limit of the thickness of the adhesive layer is about 0.5 μm or more, which is appropriate, can be about 1 μm or more, about 3 μm or more is advantageous, preferably about 7 μm or more, more preferably about 10 μm or more, further preferably about 12 μm or more (for example, greater than 12 μm), can be about 15 μm or more, and can also be about 18 μm or more. The greater the thickness of the adhesive layer, the easier it is to achieve the target adhesive force. In some ways, the thickness of the adhesive layer can be greater than 20 μm, or it can be more than 24 μm or more than 27 μm.

[0159] The adhesive sheet disclosed herein may be an adhesive sheet having adhesive layers of the above-mentioned thickness on both sides of a substrate. In addition, in a double-sided adhesive sheet with a substrate having a first adhesive layer and a second adhesive layer on each side of the substrate, the first adhesive layer and the second adhesive layer may be of the same thickness or of different thicknesses from each other.

[0160] (Surface free energy γ)

[0161] In some embodiments, the surface free energy γ of the adhesive layer is preferably less than 40 mJ / m 2 The surface free energy γ of the adhesive layer is a value expressed by the following formula: γ = γ d +γ p +γ h Here, γ in the above formula d , γ p and γ hRespectively represent the dispersion component, polar component and hydrogen bond component of the surface free energy. The surface free energy γ of the adhesive layer can be obtained by using water, diiodomethane and 1-bromonaphthalene as probe liquids, according to the contact angle of each probe liquid, according to the Kitazaki-Hata method (Journal of the Japan Adhesive Association, Vol. 8, No. 3, 1972, pp. 131-141). The contact angle can be measured using a commercially available contact angle meter. As a contact angle meter, the product name "CA-X" manufactured by Kyowa Interface Science Co., Ltd. can be used. The drop method is used for the measurement, and the contact angle is measured based on the shape of the droplet after 1500ms of dripping. The same method is also used in the examples described below.

[0162] When the surface free energy γ of the adhesive layer is reduced, there is a tendency that the wettability of the adhesive layer to the adherend is improved, and the adhesion of the interface (adhesive interface) of the adhesive layer and the adherend becomes higher. By improving the adhesion of the adhesive interface like this, it is possible to suppress the oil content and the aqueous solvent from penetrating into the above-mentioned adhesive interface from the outer edge of the adhesive sheet. Therefore, from the viewpoint of suppressing the adhesive force reduced by contact with the oil content and the aqueous solvent, it is preferred to improve the adhesion of the interface of the adhesive layer and the adherend. From the viewpoint of suppressing the adhesive force reduced by contact with the oil content and the aqueous solvent, it is preferred to improve the adhesion of the interface of the adhesive layer and the adherend.

[0163] From the viewpoint of easily obtaining higher adhesion, in some embodiments, the surface free energy γ of the adhesive layer is preferably about 35 mJ / m 2 Below, more preferably about 30mJ / m 2 Below, it can be 27mJ / m 2 Below, it can be 25mJ / m 2 Below, 20mJ / m 2 The lower limit of the surface free energy γ of the adhesive layer is not particularly limited, but is generally about 7 mJ / m 2 Above, preferably about 10 mJ / m 2 In some embodiments, the surface free energy γ of the adhesive layer can be 15 mJ / m 2 Above, it can also be 20mJ / m 2 The surface free energy γ of the pressure-sensitive adhesive layer can be adjusted by, for example, the composition of the monomer components constituting the acrylic polymer, the type and amount of the tackifier resin used, and the like.

[0164] (Gel fraction)

[0165] The gel fraction of the adhesive layer disclosed herein is not particularly limited, for example, it can be in the range of 20% to 80% (weight basis). By increasing the gel fraction of the adhesive layer within a moderate range, it is possible to impart cohesion to the adhesive layer, and suppress the reduction in adhesion caused by contact with oil and aqueous solvents. In some embodiments, it is appropriate for the gel fraction of the adhesive layer to be greater than 30%, it is advantageous to be greater than 40%, it can be greater than 45%, it can be greater than 50%, it can be more than 55%, it can be more than 60%, for example, it can be greater than 63%. In addition, from the perspective of adhesion to the adherend, in some embodiments, the gel fraction of the adhesive layer is preferably less than 75%, more preferably less than 70% (for example, less than 70%), it can be less than 68%, and it can be less than 66% by weight.

[0166] The above-mentioned gel fraction is measured by the following method. That is, about 0.1g of the adhesive sample (weight Wg1) is wrapped into a purse-shaped (turban-shaped) with a porous polytetrafluoroethylene film (weight Wg2) with an average pore size of 0.2μm, and the bag mouth is tied with a kite string (weight Wg3). As the above-mentioned porous polytetrafluoroethylene (PTFE) membrane, the trade name "NITOFLON (registered trademark) NTF1122" (average pore size 0.2μm, porosity 75%, thickness 85μm) or its equivalent available from Nitto Denko Corporation is used. The package is immersed in 50mL of ethyl acetate, kept at room temperature (about 23°C) for 7 days, the above-mentioned package is taken out, the ethyl acetate attached to the outer surface is wiped off, the package is dried at 130°C for 2 hours, and the weight of the package is measured (Wg4). The gel fraction of the adhesive layer is obtained by substituting each value into the following formula.

[0167] Gel fraction (%) = [(Wg4-Wg2-Wg3) / Wg1] × 100

[0168] (Biomass Carbon Ratio)

[0169] In some embodiments, the adhesive layer includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the adhesive layer is, for example, above 1%, above 10%, preferably above 30%, and more preferably above 50%. A high biomass carbon ratio of the adhesive indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the adhesive, the more preferred. For example, the biomass carbon ratio of the adhesive layer can be above 55%, above 60%, above 70%, above 75%, above 80%, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, and can be below 99%. From the perspective of the availability of the material, it can be below 95%, or below 90%. From the perspective of easy to exert good adhesive properties, in some embodiments, the biomass carbon ratio of the adhesive layer can be, for example, below 90%, below 85%, or below 80%.

[0170] <Base Material>

[0171] In the form of the adhesive sheet disclosed herein, which is a single-sided adhesive sheet or a double-sided adhesive sheet with a substrate, as a substrate supporting (lining) the adhesive layer, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of resin films, polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers; polyester films such as polyethylene terephthalate (PET); vinyl chloride resin films; vinyl acetate resin films; polyimide resin films; polyamide resin films; fluorine-containing resin films; cellophane, etc. As examples of paper, Japanese paper, kraft paper, cellophane, high-quality paper, synthetic paper, surface-coated paper, etc. can be listed. As examples of cloth, woven fabrics, non-woven fabrics, etc. obtained by spinning various fibrous materials alone or in blends can be listed. As the above-mentioned fibrous materials, examples can be: cotton, staple fibers, Manila hemp, pulp, rayon, acetate fibers, polyester fibers, polyvinyl alcohol fibers, polyamide fibers, polyolefin fibers, etc. Examples of rubber sheets include natural rubber sheets, butyl rubber sheets, etc. Examples of foam sheets include foamed polyolefin sheets, foamed polyurethane sheets, foamed chloroprene rubber sheets, etc. Examples of metal foils include aluminum foil, copper foil, etc. It should be noted that the substrate supporting the adhesive layer is also referred to as a substrate layer in the adhesive sheet.

[0172] The substrate may be formed of a biomass-derived material or a non-biomass-derived material. From the viewpoint of producing a PSA sheet that reduces dependence on fossil resource materials, it is preferred to use a biomass-derived substrate material (typically a resin film).

[0173] In addition, the substrate can also be formed using recyclable materials, recycled materials (also referred to as regenerated materials). As the regenerated material, a resin film is preferably used. Since the resin film (for example, polyester films such as PET films) can be reused, whether or not materials from plants are used, continuous reproduction can be carried out by reusing the used resin film, and the environmental load can be reduced. Such reusable resin films and recycled resin films are also referred to as regenerated films. The above-mentioned regenerated materials (for example, regenerated films) can be formed from materials from biomass, and can also be formed from materials that are not from biomass.

[0174] As the substrate constituting the adhesive sheet with substrate, a substrate containing a resin film as a base film can be preferably used. The above-mentioned base film is typically a (non-dependent) member that can independently maintain a shape. The substrate in the technology disclosed herein can be substantially composed of such a base film. Alternatively, the above-mentioned substrate can also include an auxiliary layer in addition to the above-mentioned base film. As examples of the above-mentioned auxiliary layers, a colored layer, a reflective layer, a primer layer, an antistatic layer, etc. arranged on the surface of the above-mentioned base film can be cited.

[0175] The resin film is a film having a resin material as a main component (for example, a component with a content greater than 50% by weight in the resin film). Examples of resin films include: polyolefin resin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers; polyester resin films such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); vinyl chloride resin films; vinyl acetate resin films; polyimide resin films; polyamide resin films; fluorine-containing resin films; cellophane; etc. The resin film may be a rubber film such as a natural rubber film or a butyl rubber film. Among them, from the viewpoint of operability and processability, a polyester film is preferred, and a PET film is particularly preferred.

[0176] It should be noted that, in this specification, "resin film" is typically a non-porous sheet, which is a concept different from so-called non-woven fabrics and woven fabrics (in other words, a concept other than non-woven fabrics and woven fabrics). The above-mentioned resin film can be any one of a non-stretched film, a uniaxially stretched film, and a biaxially stretched film. In addition, such a resin film can be non-foamed. Here, a non-foamed resin film refers to a resin film that has not been intentionally treated to form a foam body. Specifically, a non-foamed resin film can be a resin film having a foaming ratio of less than 1.1 times (for example, less than 1.05 times, typically less than 1.01 times).

[0177] The above-mentioned base material (e.g., resin film) may be mixed with various additives such as fillers (inorganic fillers, organic fillers, etc.), colorants, dispersants (surfactants, etc.), anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, etc. as needed. The mixing ratio of various additives may be less than about 30% by weight (e.g., less than about 20% by weight, typically less than about 10% by weight).

[0178] The above-mentioned substrate (e.g., resin film) may be a single-layer structure, or may have a multilayer structure of two, three or more layers. From the viewpoint of shape stability, the substrate is preferably a single-layer structure. In the case of a multilayer structure, it is preferred that at least one layer (preferably all layers) is a layer having a continuous structure of the above-mentioned resin (e.g., polyester resin). The manufacturing method of the substrate (typically a resin film) may appropriately adopt a conventionally known method without particular limitation. For example, conventionally known film forming methods such as extrusion molding, inflation molding, T-die casting molding, and calendering roll molding may be appropriately adopted.

[0179] The surface of the substrate may be subjected to conventionally known surface treatments such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and primer application. Such surface treatments may be used to improve the adhesion between the substrate and the adhesive layer, in other words, the anchoring property of the adhesive layer to the substrate.

[0180] In addition, when the technology disclosed herein is implemented in the form of a single-sided adhesive sheet with a substrate, a peeling treatment can be applied to the back of the substrate as needed. The peeling treatment can be, for example, a treatment in which a conventional silicone-based, long-chain alkyl-based, fluorine-containing type or other peeling agent is applied to a film-like shape of typically about 0.01 μm to about 1 μm (for example, 0.01 μm to 0.1 μm). By implementing this peeling treatment, an effect such as easy unwinding of a roll-shaped roll of the adhesive sheet can be obtained.

[0181] In the adhesive sheet of the method including substrate, the thickness of the substrate is not particularly limited. From the viewpoint of avoiding the adhesive sheet from becoming too thick, the thickness of the substrate can be, for example, about 200 μm or less, preferably about 150 μm or less, and more preferably about 100 μm or less. According to the purpose of use and the method of use of the adhesive sheet, the thickness of the substrate can be about 70 μm or less, or about 50 μm or less, or about 30 μm or less (for example, about 25 μm or less). In some ways, the thickness of the substrate film layer can be about 20 μm or less, or about 15 μm or less, or about 10 μm or less (for example, about 5 μm or less). By reducing the thickness of the substrate, even if the total thickness of the adhesive sheet is the same, the thickness of the adhesive layer can be further increased. From the viewpoint of improving the adhesion to the adherend and the substrate, it is advantageous to further increase the thickness of the adhesive layer. The lower limit of the substrate is not particularly limited. From the viewpoint of the operability (handleability) and processability of the adhesive sheet, the thickness of the substrate is appropriately about 0.5 μm or more (e.g., 1 μm or more), preferably about 2 μm or more, for example, about 6 μm or more, about 8 μm or more, or about 10 μm or more. In some embodiments, the thickness of the substrate can be about 15 μm or more, or about 25 μm or more.

[0182] <Release liner>

[0183] In the technology disclosed herein, a release liner can be used when forming an adhesive layer, making an adhesive sheet, storing, circulating, shaping, etc. the adhesive sheet before use. As a release liner, there is no particular limitation, for example, a release liner having a release treatment layer on the surface of a liner substrate such as a resin film or paper; a release liner containing a fluorine-containing polymer (polytetrafluoroethylene, etc.), etc. can be used. The above-mentioned release treatment layer can be formed by surface treating the above-mentioned liner substrate with a release treatment agent such as silicone, long-chain alkyl, fluorine-containing, molybdenum sulfide, etc. As a liner substrate, as with the substrate of the aforementioned adhesive sheet, a substrate formed using a material from biomass, a recycled material (recycled film, etc.) can be preferably used.

[0184] <Total Thickness of Adhesive Sheet>

[0185] The total thickness of the adhesive sheet disclosed herein (including an adhesive layer and a substrate layer, but not including a release liner) is not particularly limited. The total thickness of the adhesive sheet can be, for example, about 1 mm or less, about 500 μm or less, about 300 μm or less, and from the perspective of thinning, about 200 μm or less is appropriate, and can be about 150 μm or less (for example, about 100 μm or less). In some preferred embodiments, the thickness of the adhesive sheet can be about 70 μm or less, for example, about 55 μm or less. The lower limit of the thickness of the adhesive sheet is, for example, 0.1 μm or more (for example, 0.5 μm or more), about 3 μm or more is appropriate, preferably about 10 μm or more, more preferably about 15 μm or more, about 20 μm or more, and about 40 μm or more. An adhesive sheet having a thickness above a specified value is easy to obtain adhesion to an adherend, and in addition, has a tendency to be excellent in operability. It should be noted that in an adhesive sheet without a substrate, the thickness of the adhesive layer is the total thickness of the adhesive sheet.

[0186] <Characteristics of Adhesive Sheet>

[0187] (Adhesion to SUS (initial adhesion F0))

[0188] In some embodiments of the adhesive sheet disclosed herein, the 180-degree peel strength (adhesion to SUS) of the adhesive sheet to the stainless steel plate is preferably 8.0N / 10mm or more. An adhesive sheet showing such adhesion to SUS can exert good fixing performance, for example, in the purpose of fixing components. The above-mentioned adhesion to SUS is more preferably about 8.2N / 10mm or more, further preferably 8.5N / 10mm or more, can be 8.8N / 10mm or more, can be 9.0N / 10mm or more, can be 9.2N / 10mm or more, can be 9.5N / 10mm or more, can be 9.7N / 10mm or more. In the fixation of small or narrow components, and in the fixation of components that can apply a relatively large load to the joint due to their own weight or external force, a higher adhesion to SUS is advantageous. There is no particular restriction on the upper limit of the above-mentioned SUS adhesion. Considering the balance with other requirements (such as thinning of the adhesive layer, etc.), it can be, for example, 20N / 10mm or less, 18N / 10mm or less, or 16N / 10mm or less. The above-mentioned SUS adhesion is measured using a SUS plate as the adherend under a measurement environment of 23°C and 50%RH, at a pulling speed of 300mm / min and a peeling angle of 180 degrees. The above-mentioned SUS adhesion is a property measured after being pasted to the adherend without supplying oil or aqueous solvent. In order to express the adhesion F after immersion described later A 、F BThe above-mentioned adhesive force to SUS is sometimes referred to as "initial adhesive force F0" hereinafter. The initial adhesive force F0 is more specifically measured by the method described in the examples described later.

[0189] (Adhesion retention rate R A )

[0190] In some aspects of the adhesive sheet disclosed herein, the adhesive sheet is represented by the following formula:

[0191] Adhesion retention rate R A [%] = (adhesion after immersion F A / Initial adhesion F0) × 100

[0192] The adhesion retention rate R A Preferably, it is 60% or more. Here, the post-immersion adhesive force F in the above formula A The 180-degree peel strength is measured after the PSA sheet to be evaluated is attached to a stainless steel plate and immersed in oleic acid at 40°C and 90% RH for 2 weeks. The initial adhesive force F0 in the above formula is the above-mentioned adhesive force to SUS. A More specifically, the measurement is performed by the method described in the examples described below. A According to the above-mentioned adhesion F after immersion A And the above initial adhesive force F0 is calculated by the above formula.

[0193] From the viewpoint of better suppressing the decrease in adhesive force due to contact with oil, in some embodiments, the adhesive force retention rate R A It is more preferably 63% or more (e.g. 65% or more), further preferably 67% or more (e.g. 70% or more), and may be 73% or more, 75% or more, 80% or more, or 85% or more. Adhesion retention rate R A There is no particular upper limit on the adhesion retention rate R A Typically, it is 100% or less. From the perspective of easiness in taking into account other characteristics (e.g., initial adhesion F0, water solvent resistance), in some embodiments, it may be, for example, 98% or less, 95% or less, 90% or less, 85% or less, or 80% or less. In addition, in some embodiments, from the perspective of bonding reliability in contact with oil, the above-mentioned post-immersion adhesion F0 may be 98% or less, 95% or less, 90% or less, 85% or less, or 80% or less. AIt is preferably 4.8 N / 10 mm or more (e.g. 5.0 N / 10 mm or more), more preferably 5.3 N / 10 mm or more (e.g. 5.5 N / 10 mm or more), further preferably 6.0 N / 10 mm or more, 6.5 N / 10 mm or more, 7.0 N / 10 mm or more, or 7.5 N / 10 mm or more. Adhesion force after immersion F A There is no particular upper limit on the value of . In some embodiments, the post-immersion adhesion F0 is preferably 0.0045mm / s, and the post-immersion adhesion F0 is preferably 0.0050mm / s. A For example, it may be 19 N / 10 mm or less, 17 N / 10 mm or less, or 15 N / 10 mm or less.

[0194] (Adhesion retention rate R B )

[0195] In some aspects of the adhesive sheet disclosed herein, the adhesive sheet is of the following formula:

[0196] Adhesion retention rate R B [%] = (adhesion after immersion F B / Initial adhesion F0) × 100

[0197] The adhesion retention rate R B Preferably, it is 70% or more. Here, the post-immersion adhesive force F in the above formula B The 180-degree peel strength is measured after the adhesive sheet to be evaluated is attached to a stainless steel plate and immersed in a 50% isopropyl alcohol aqueous solution (a mixed solvent with a volume ratio of 1:1) at 40°C and 90% RH for 2 weeks. The initial adhesive force F0 in the above formula is the above-mentioned adhesive force to SUS. Adhesion force F after immersion B More specifically, the measurement is performed by the method described in the examples described below. B According to the above-mentioned adhesion F after immersion B And the above initial adhesive force F0 is calculated by the above formula.

[0198] From the viewpoint of better suppressing the decrease in adhesive force due to contact with an aqueous solvent (e.g., an aqueous solvent such as water, a lower alcohol, or a mixed solvent of water and a lower alcohol), in some embodiments, the adhesive force retention rate R B It is preferably 75% or more, more preferably 80% or more, further preferably 84% or more (eg 85% or more), and may be 87% or more, or 90% or more. B There is no particular upper limit on the adhesion retention rate R BTypically, it is 100% or less. From the perspective of easiness in taking into account other characteristics (e.g., initial adhesion F0, oil resistance), in some embodiments, it may be, for example, 99% or less, 98% or less, 96% or less, 95% or less, or 94% or less. In addition, in some embodiments, from the perspective of bonding reliability in contact with an aqueous solvent, the above-mentioned post-immersion adhesion F0 may be 99% or less, 98% or less, 96% or less, 95% or less, or 94% or less. B It is preferably 6.0 N / 10 mm or more (e.g. 6.5 N / 10 mm or more), more preferably 7.0 N / 10 mm or more (e.g. 7.5 N / 10 mm or more), further preferably 8.0 N / 10 mm or more, 8.2 N / 10 mm or more, 8.5 N / 10 mm or more, or 8.7 N / 10 mm or more. Adhesion force after immersion F B There is no particular upper limit on the value of . In some embodiments, the post-immersion adhesion F0 is preferably 0.0045mm / s, and the post-immersion adhesion F0 is preferably 0.0050mm / s. B For example, it may be 19 N / 10 mm or less, 18 N / 10 mm or less, 17 N / 10 mm or less, or 15 N / 10 mm or less.

[0199] In some embodiments, the adhesive sheet includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the adhesive sheet is, for example, 1% or more, 10% or more, preferably 30% or more, and more preferably 50% or more. The high biomass carbon ratio of the adhesive sheet indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the adhesive sheet, the more preferred. For example, the biomass carbon ratio of the adhesive sheet can be 55% or more, 60% or more, 70% or more, 75% or more, 80% or more, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, and can be 99% or less. From the perspective of the availability of the material, it can be 95% or less, or 90% or less. From the perspective of easy to play a good adhesive performance, in some embodiments, the biomass carbon ratio of the adhesive sheet can be, for example, 90% or less, 85% or less, or 80% or less.

[0200] <Purpose>

[0201] The purpose of the adhesive sheet disclosed herein is not particularly limited and can be used for various purposes. The adhesive sheet disclosed herein utilizes the characteristics that can take into account the adhesive force, oil resistance and water resistance solvent resistance at a high level, and can be preferably used for fixing the various components that can contact with one or both of oil and aqueous solvent. As a representative example of such purposes, the purposes of fixing parts in various portable devices (portable devices) can be listed. For example, it is suitable for the fixed use of parts in portable electronic devices. Non-limiting examples of the above-mentioned portable electronic devices include: mobile phones, smart phones, tablet personal computers, notebook personal computers, various wearable devices (for example, wrist-worn types worn on the wrist like watches, modular types worn on a part of the body with clips, straps, etc., eyewear types including glasses (monocular types, binocular types. Also including helmet types.), clothing types worn on shirts, socks, hats, etc. in the form of accessories, ear-worn types worn on the ears like headphones, etc.), digital cameras, digital video cameras, audio equipment (portable music players, voice recorders, etc.), calculators (desktop calculators, etc.), portable game devices, electronic dictionaries, electronic notepads, electronic books, in-vehicle information equipment, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. Non-limiting examples of portable devices other than portable electronic devices include: mechanical watches, pocket watches, flashlights, handheld mirrors, card holders, etc. It should be noted that in this specification, it is not sufficient to interpret "portable" as merely being able to be carried. In essence, it has portability at a level that an individual (standard adult) can move it relatively easily.

[0202] Figure 4 Schematically shows an example of a portable electronic device (smartphone) using the adhesive sheet disclosed herein. Figure 4 As shown, a battery (heating element) 540 is built into the interior of the housing 520 of the portable electronic device 500. In addition, the portable electronic device 500 is composed of an adhesive sheet 550. In this configuration example, the adhesive sheet 550 has the form of a double-sided adhesive sheet (double-sided adhesive sheet) that fixes the components constituting the portable electronic device 500. It should be noted that the portable electronic device 500 has a touch panel 570 in which the display part also functions as an input part. The adhesive sheet disclosed herein can be preferably used as a constituent element (component bonding means) of the portable electronic device as described above.

[0203] In addition, the adhesive sheet disclosed herein may have an adhesive layer containing an acrylic polymer with a high biomass carbon ratio in some embodiments, and thus can be used as a substitute for conventional acrylic adhesives (i.e., acrylic adhesives with a low biomass carbon ratio) in various applications using the acrylic adhesive, thereby helping to reduce dependence on fossil resource materials. The adhesive sheet disclosed herein can be preferably used as an adhesive sheet with reduced dependence on fossil resource materials.

[0204] Matters disclosed by this specification include the following.

[0205] [1] A pressure-sensitive adhesive sheet, comprising a pressure-sensitive adhesive layer comprising an acrylic polymer and a tackifier resin, wherein the acrylic polymer is a polymer containing a monomer component of n-heptyl acrylate, the content of the tackifier resin is greater than 10 parts by weight relative to 100 parts by weight of the acrylic polymer, and the pressure-sensitive adhesive layer has a swelling degree of 100 or less in ethyl acetate.

[0206] [2] The pressure-sensitive adhesive sheet according to [1] above, wherein the monomer component contains 5.0% by weight or more of a carboxyl group-containing monomer.

[0207] [3] The adhesive sheet according to [1] or [2] above, wherein the adhesive composition for forming the adhesive layer contains an isocyanate crosslinking agent and an epoxy crosslinking agent in combination.

[0208] [4] The pressure-sensitive adhesive sheet according to any one of [1] to [3] above, wherein the pressure-sensitive adhesive layer contains a phenolic tackifier resin as the tackifier resin.

[0209] [5] The pressure-sensitive adhesive sheet according to [4] above, comprising a terpene phenol resin as the phenolic tackifier resin, wherein the content of the terpene phenol resin is 20 parts by weight or more based on 100 parts by weight of the acrylic polymer.

[0210] [6] The pressure-sensitive adhesive sheet according to any one of [1] to [5] above, wherein the acrylic polymer has a weight average molecular weight of greater than 500,000.

[0211] [7] The adhesive sheet according to any one of [1] to [6] above, wherein the adhesive sheet has a 180-degree peel strength with respect to a stainless steel plate of 8.0 N / 10 mm or more.

[0212] [8] The PSA sheet according to any one of [1] to [7] above, wherein the PSA sheet is a double-sided PSA sheet.

[0213] [9] The PSA sheet according to any one of [1] to [8] above, which is a double-sided PSA sheet having a resin film as a supporting substrate and the PSA layer provided on one surface and the other surface of the supporting substrate.

[0214]

[10] The pressure-sensitive adhesive sheet according to any one of [1] to [9] above, wherein the pressure-sensitive adhesive sheet is used to fix a component in a portable device.

[0215]

[11] A portable device, wherein an adhesive sheet is bonded to a component constituting the electronic device, the adhesive sheet having an adhesive layer comprising an acrylic polymer and a tackifier resin, the acrylic polymer being a polymer containing a monomer component of n-heptyl acrylate, the tackifier resin content being greater than 10 parts by weight relative to 100 parts by weight of the acrylic polymer, and the degree of swelling of the adhesive layer in ethyl acetate being less than 100.

[0216]

[12] The portable device according to

[11] above, wherein the portable device is a portable electronic device.

[0217]

[13] The portable device according to

[11] or

[12] above, wherein the monomer component of the acrylic polymer contains 5.0% by weight or more of a carboxyl group-containing monomer.

[0218]

[14] The portable device according to any one of

[11] to

[13] above, wherein the adhesive composition used to form the adhesive layer comprises an isocyanate crosslinking agent and an epoxy crosslinking agent.

[0219]

[15] The portable device according to any one of

[11] to

[14] above, wherein the adhesive layer contains a phenolic tackifier resin as the tackifier resin.

[0220]

[16] The portable device according to

[15] above, wherein the phenolic tackifier resin comprises a terpene phenol resin, and the content of the terpene phenol resin is 20 parts by weight or more relative to 100 parts by weight of the acrylic polymer.

[0221]

[17] The portable device according to any one of

[11] to

[16] above, wherein the weight average molecular weight of the acrylic polymer is greater than 500,000.

[0222]

[18] The portable device according to any one of

[11] to

[17] above, wherein the 180-degree peel strength of the adhesive sheet to the stainless steel plate is 8.0 N / 10 mm or more.

[0223]

[19] The portable device according to any one of

[11] to

[18] above, wherein the portable device is configured as a double-sided adhesive sheet.

[0224]

[20] A portable device according to any one of

[11] to

[19] above, wherein the adhesive sheet is configured as a double-sided adhesive sheet having a resin film as a supporting substrate and the adhesive layer provided on one surface and the other surface of the supporting substrate.

[0225] Example

[0226] Hereinafter, some embodiments of the present invention will be described, but it is not intended to limit the present invention to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are weight references.

[0227] <Evaluation method>

[0228] (Initial Adhesion F0)

[0229] Under a measurement environment of 23° C. and 50% RH, a 50 μm thick PET film was attached to one adhesive surface of a PSA sheet (double-sided PSA sheet) for backing, and the sample was cut into a size of 10 mm in width and 100 mm in length to prepare a measurement sample.

[0230] Under the environment of 23°C and 50%RH, a 2kg roller was reciprocated once to press the other adhesive surface of the above-mentioned test sample onto the surface of a stainless steel plate (SUS304 BA plate) cleaned with ethyl acetate. It was left in the same environment for 30 minutes, and then the peel strength (initial adhesive force F0) [N / 10mm] was measured using a tensile tester according to JIS Z0237:2000 at a pulling speed of 150mm / min and a peeling angle of 180 degrees.

[0231] (Oil resistance)

[0232] Under a measurement environment of 23° C. and 50% RH, a 50 μm thick PET film was attached to one adhesive surface of a PSA sheet (double-sided PSA sheet) for backing, and the sample was cut into a size of 10 mm in width and 100 mm in length to prepare a measurement sample.

[0233] In an environment of 23°C and 50% RH, a 2kg roller is moved back and forth once to press the other adhesive surface of the above-mentioned test sample onto the surface of a stainless steel plate (SUS304 BA plate) cleaned with ethyl acetate. It is placed in the same environment for 30 minutes, and then immersed in an oleic acid bath and kept for 2 weeks in an environment of 40°C and 90% RH. Then, the above-mentioned test sample is lifted from the oleic acid bath, and the oleic acid attached to the surrounding is gently wiped off. It is placed in an environment of 23°C and 50% RH for 30 minutes, and then a tensile tester is used to measure the peel strength after oleic acid immersion (adhesion after immersion F) under the conditions of a pulling speed of 150 mm / min and a peeling angle of 180 degrees according to JIS Z0237:2000. A )[N / 10mm].

[0234] The adhesion retention rate R was calculated from the measured values ​​obtained by the following formula: A :

[0235] Adhesion retention rate R A [%] = (adhesion after immersion F A / initial adhesion F0)×100.

[0236] (Water resistance and solvent resistance)

[0237] The results are shown in Table 1. The results are shown in Table 2. The results are shown in Table 3. The results are shown in Table 4. The results are shown in Table 5. The results are shown in Table 6. A The peel strength after immersion in an aqueous solvent (adhesion after immersion F B )[N / 10mm].

[0238] The adhesion retention rate R was calculated from the measured values ​​obtained by the following formula: B :

[0239] Adhesion retention rate R B [%] = (adhesion after immersion F B / initial adhesion F0)×100.

[0240] (Swelling degree)

[0241] About 0.1 g of adhesive sample (weight W S1 ) using a porous polytetrafluoroethylene membrane with an average pore size of 0.2 μm (weight W S2) is wrapped into a purse shape, and the bag mouth is tied with a kite string (weight Ws3). As the above-mentioned porous polytetrafluoroethylene (PTFE) membrane, the trade name "NITOFLON (registered trademark) NTF1122" (average pore size 0.2μm, porosity 75%, thickness 85μm) available from Nitto Denko Corporation or its equivalent is used. The package is immersed in 50mL of ethyl acetate and kept at room temperature (about 23°C) for 7 days. Then, the above-mentioned package is taken out, the ethyl acetate attached to the outer surface is wiped off, and the weight of the package (Ws3) is measured. S4 ). Next, the package was dried at 130° C. for 2 hours, and the weight of the package was measured (Wg5). The swelling degree of the adhesive layer was determined by substituting each value into the following formula.

[0242] Swelling degree = (W S4 -W S2 -W S3 ) / (W S5 -W S2 -W S3 )

[0243] <Example 1>

[0244] (Synthesis of Acrylic Polymer)

[0245] 96 parts of n-heptyl acrylate (n-HpA) as a monomer component, 4 parts of acrylic acid (AA) and ethyl acetate as a polymerization solvent were added to a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, and stirred for 2 hours while introducing nitrogen. By doing so, oxygen in the polymerization system was removed, and then 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator was added, and solution polymerization was carried out at 60°C to 70°C for 8 hours to obtain a solution of an acrylic polymer (A1). The weight average molecular weight (Mw) of the acrylic polymer (A1) is 900,000. It should be noted that the above-mentioned n-HpA is a compound having a heptyl group from biomass at the ester end synthesized using heptanol from biomass.

[0246] (Preparation of Adhesive Composition)

[0247] 100 parts of the above-mentioned acrylic polymer (A1), 30 parts of tackifier resin B (trade name "YS Polystar S145", manufactured by Yasuhara Chemical Co., Ltd., terpene phenol resin, softening point 145°C, hydroxyl value 70 mgKOH / g to 110 mgKOH / g), 3 parts of isocyanate crosslinking agent (solid content basis, the same below), and 0.03 parts of epoxy crosslinking agent were stirred and mixed to prepare the adhesive composition of this example. As the above-mentioned isocyanate crosslinking agent, the trade name "CORONATE L" (75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct) manufactured by Tosoh Corporation was used, and as the above-mentioned epoxy crosslinking agent, the trade name "TETRAD-C" (1,3-bis(N,N-diglycidylaminomethyl)cyclohexane) manufactured by Mitsubishi Gas Chemical Co., Ltd. was used.

[0248] (Manufacturing of adhesive sheet)

[0249] Prepare two polyester release films (trade name "DIAFOIL MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm. Apply the above-mentioned adhesive composition on the release surface of these release films and dry them at 100°C for 2 minutes to form an adhesive layer with a thickness of 19 μm. The adhesive layer formed on the above-mentioned two release films is respectively attached to the first and second surfaces of a PET film (trade name "Lumirror", manufactured by Toray Corporation) with a thickness of 12 μm as a substrate. The above-mentioned release film remains on the adhesive layer as it is and is used to protect the surface (adhesive surface) of the adhesive layer. By doing so, a double-sided adhesive sheet with a thickness of 50 μm with a substrate is obtained, in which the two adhesive surfaces are protected by the above-mentioned two polyester release films.

[0250] <Example 2>

[0251] In the preparation of the adhesive composition of Example 1, tackifier resin A (trade name "YS Polystar T115", manufactured by Yasuhara Chemical Co., Ltd., terpene phenol resin, softening point 115°C, hydroxyl value 60 mgKOH / g) was used instead of tackifier resin B. A double-sided adhesive sheet with a substrate of this example was prepared in the same manner as in Example 1 except that the obtained adhesive composition was used.

[0252] <Example 3 to Example 9>

[0253] The monomer composition was changed to 94 parts of n-HpA and 6 parts of AA, and the concentration of the monomer components during polymerization was adjusted. In the same manner as the synthesis of the acrylic polymer (A1), a solution of the acrylic polymer (A2) was obtained. The above acrylic polymer (A2) was used, and the composition was changed to that shown in Table 1. In the same manner as in Example 1, the adhesive composition of each example was prepared, and the double-sided adhesive sheet with a substrate of each example was prepared using the adhesive composition. As the tackifier resin C shown in Table 1, the trade name "PENSEL D125" (polymerized rosin pentaerythritol ester, softening point 125°C, hydroxyl value 34 mgKOH / g) manufactured by Arakawa Chemical Industries, Ltd. was used.

[0254] <Example 10 to Example 12>

[0255] The monomer composition was changed to 90 parts of n-HpA and 10 parts of AA, and the concentration of the monomer components during polymerization was adjusted. In the same manner as the synthesis of the acrylic polymer (A1), a solution of the acrylic polymer (A3) was obtained. The above acrylic polymer (A3) was used, and the composition was changed to that shown in Table 1. In the same manner as Example 1, adhesive compositions of each example were prepared, and double-sided adhesive sheets with substrates of each example were prepared using the adhesive compositions.

[0256] <Comparative Example 1-Comparative Example 2>

[0257] The PSA composition of this example was prepared in the same manner as in Example 5 except that the amount of tackifier resin A used was set to 0 parts (Comparative Example 1) or 5 parts (Comparative Example 2), and the double-sided PSA sheet with substrate of this example was produced using the PSA composition.

[0258] <Comparative Example 3 to Comparative Example 4>

[0259] A solution of acrylic polymer (A4) was obtained in substantially the same manner as the synthesis of acrylic polymer (A1), except that the monomer composition was changed to 90 parts of 2-ethylhexyl acrylate (2EHA) and 10 parts of AA. The above acrylic polymer (A4) was used, but the composition was changed to that shown in Table 2. In the same manner as in Example 1, adhesive compositions of each example were prepared, and double-sided adhesive sheets with substrates of each example were prepared using the adhesive compositions.

[0260] <Comparative Example 5>

[0261] A solution of acrylic polymer (A5) was obtained in substantially the same manner as the synthesis of acrylic polymer (A1), except that the monomer composition was changed to 95 parts of n-butyl acrylate (BA) and 5 parts of AA. The above acrylic polymer (A5) was used, and except that the composition was changed to that shown in Table 2, the adhesive composition of this example was prepared in the same manner as in Example 1, and the double-sided adhesive sheet with substrate of this example was prepared using the adhesive composition.

[0262] Tables 1 and 2 show the outlines and evaluation results of the pressure-sensitive adhesive sheets of each example.

[0263]

[0264]

[0265] As shown in Table 1, the PSA layers of Examples 1 to 12 contain an acrylic polymer containing n-heptyl acrylate as a monomer component and a tackifier resin in an amount greater than 10 parts per 100 parts of the acrylic polymer, and have a swelling degree in ethyl acetate of 100 or less. The initial adhesive force F0 and the adhesive force retention rate R to oil of the PSA sheets of these Examples are as follows: A and the adhesion retention rate R to aqueous solvents B That is, the adhesive strength, oil resistance and water solvent resistance are all achieved at a high level. It should be noted that the surface free energy γ of the adhesive layer of Examples 1 to 12 is all within 10 mJ / m 2 ~35mJ / m 2 within the range.

[0266] In contrast, as shown in Table 2, the initial adhesive force F0 of the adhesive sheets of Comparative Example 1 containing no tackifier resin and Comparative Example 2 containing a small amount of tackifier resin was low. Comparative Examples 3 and 4 are examples in which n-heptyl acrylate was not contained and an acrylic polymer containing 2EHA as a main monomer component was used. The initial adhesive force F0 of Comparative Example 3 was low, and in Comparative Example 4 containing an increased amount of tackifier resin, the initial adhesive force F0 increased, but the swelling degree was much greater than 100, and the adhesive force retention rate R to oil was 0. A Comparative Example 5 is an example of using an acrylic polymer as a polymer containing no n-heptyl acrylate and having BA as a main monomer component, and the resistance to aqueous solvents is insufficient.

[0267] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.

[0268] Description of symbols

[0269] 1, 2, 3 adhesive sheets

[0270] 10 Support substrate

[0271] 10A first side

[0272] 10B Second side (back side)

[0273] 21 Adhesive layer (first adhesive layer)

[0274] 21A bonding surface (first bonding surface)

[0275] 21B Second adhesive surface

[0276] 22 Adhesive layer (second adhesive layer)

[0277] 22A bonding surface (second bonding surface)

[0278] 31, 32 Release liner

[0279] 100, 200, 300 adhesive sheets with release liner

Claims

1. An adhesive sheet, wherein: The adhesive sheet has an adhesive layer containing an acrylic polymer and a tackifying resin. The acrylic polymer is a polymer containing a monomer component of n-heptyl acrylate, The content of the tackifying resin is greater than 10 parts by weight relative to 100 parts by weight of the acrylic polymer. The adhesive layer has a swelling degree of 100 or less in ethyl acetate.

2. The adhesive sheet according to claim 1, wherein The monomer component contains 5.0% by weight or more of a carboxyl group-containing monomer.

3. The adhesive sheet according to claim 1 or 2, wherein The adhesive composition for forming the adhesive layer includes an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent in combination.

4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The adhesive layer includes a phenolic tackifying resin as the tackifying resin.

5. The adhesive sheet according to claim 4, wherein comprising a terpene phenol resin as the phenolic tackifying resin, The content of the terpene phenol resin is 20 parts by weight or more based on 100 parts by weight of the acrylic polymer.

6. The pressure-sensitive adhesive sheet according to any one of claims 1 to 5, wherein The weight average molecular weight of the acrylic polymer is greater than 500,000.

7. The pressure-sensitive adhesive sheet according to any one of claims 1 to 6, wherein The adhesive sheet has a 180-degree peel strength to a stainless steel plate of 8.0 N / 10 mm or more.

8. The pressure-sensitive adhesive sheet according to any one of claims 1 to 7, wherein The PSA sheet is configured as a double-sided PSA sheet including a resin film as a supporting substrate and the PSA layer provided on one surface and the other surface of the supporting substrate.

9. The pressure-sensitive adhesive sheet according to any one of claims 1 to 8, wherein The adhesive sheet is used for fixing components in portable devices.

Citation Information

Patent Citations

  • Adhesive sheet

    JP2017132911A

  • Adhesive sheet

    JP2017165977A

  • Vehicle control system and server device

    JP2022108034A

  • Adhesive tape

    CN101935508A

  • Adhesive sheet

    CN107011817A